Tissue-adherent chitosan materials that resist dissolution
Through the catechol-modified chitosan material, the problem of difficulty in maintaining integrity and adhesion in the body is solved, and long-term stability and effective hemostatic effect in harsh environments are achieved.
Patent Information
- Application Number
- CN201880090516.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-15
- Filing Date
- 2018-12-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2038-12-28
Smart Images

Figure CN111787892B_ABST
Abstract
Description
[0001] Government franchise rights
[0002] This invention was made with government support under Grants R42DK078400 and R44DK104564 awarded by the National Institute of Diabetes and Digestive and Kidney Diseases. The government has certain rights in this invention. background Technical Field
[0004] The safe, reliable and effective delivery of bioactive chitosan materials in vivo is still a major problem. In use, bioactive chitosan materials must keep complete at least 12 hours period in the presence of biological fluids, such as gastric juice, blood, bile and urine, and must be able to adhere to tissue, including that the internal elastic layer of gastrointestinal mucosa and vascular system exceeds 24 hours period. Bioactive chitosan has many applications in vivo, is not limited to drug delivery, hemostasis, wound healing, tissue regeneration and embolism therapy. The current chitosan materials used on the body or in vivo and the compositions of chitosan materials are limited in their application, because they cannot resist dissolving and rapid loss in harsh environments, such as in the stomach and because of its adhesion to tissue and cannot be maintained in situ.
[0005] The present disclosure relates to the field of chitosan materials comprising catechol-modified chitosan and uses thereof.
[0006] Description of Related Art
[0007] There are many surgeries on vascular organs and tissues, such as the heart, liver, pancreas, stomach, intestines, colon, prostate, tonsils, ears, nose, throat, and brain, which often continue to bleed after injury and through wound healing. Unless standard hemostasis is applied, the initial injury may continue to bleed for several days, and bleeding may also recur at a later time. The initial standard of care for hemostasis of postoperative bleeding varies depending on the type of surgery. Bandages, gauze packs, biological dressings, cautery, and ligatures can be applied to locally address the problem. If bleeding continues, a bandaging period of up to 24 hours may be required. If bleeding cannot be controlled after a period of conservative management, the patient may have to return to the surgical operating room immediately for hemostasis by open or endoscopic surgery. Despite advances in hemostasis using advanced dressings, none of these advances have translated into reliable treatment options under unique surgical conditions where delivery, tissue adhesion, and continued bleeding are extremely challenging and are compounded with other biofluid considerations. Rapid hemostasis is highly desirable in any setting.
[0008] Minimally invasive surgical procedures are becoming the preferred mode of interventional treatment, due to the ability to access body areas with significantly reduced risks (compared to open surgery) with lower morbidity, lower hospitalization costs and less patient discomfort. Advanced biomaterials have become the most cutting-edge technology to address current limitations and are able to improve safety, reliability and increase the practice and application of minimally invasive surgical procedures. Current limitations in minimally invasive surgical procedures include controlling bleeding (especially bleeding), non-invasive and delicate suturing of soft tissue sites, local promotion of healing, local treatment of pathogenic diseases, and local placement of anchoring or adhesion at the surgical / intervention site. More recently, minimally invasive interventions have been used to address vascular pathogenesis, including vascular malformations, aneurysms, and vascular tumors. The preferred surgery for addressing vascular malformations, aneurysms, and vascular tumors is to use embolization therapy to close abnormal blood vessels. Embolization therapy involves the local delivery of a closure device, such as a coil of a stent or material or an anchored biomaterial, which can remain in place for an extended period of time to promote the formation of a large amount of clots and then permanently close the blood vessel.
[0009] Biocompatible tissue adhesive chitosan materials that can remain intact for extended periods of time and promote local clot formation and normal tissue healing have advanced material properties that could provide significant advances in surgical practice.
[0010] In addition, prolonged bleeding and its associated mortality and morbidity risks remain a serious problem in the gastrointestinal (GI) tract. Techniques and devices that can provide rapid hemostasis of gastrointestinal bleeding (GIB) for upper gastrointestinal bleeding (UGIB) and lower gastrointestinal bleeding (LGIB) are needed. Current hemostasis during and after transurethral resection of the prostate (TURP) relies on cautery for small vessel arterial bleeding and applying balloon pressure to resolve venous oozing. Both the bladder neck and the prostate are highly vascularized tissues that usually continue to bleed after injury and during wound healing. Unless standard hemostasis is performed, the initial injury site may continue to bleed for several days, and the bleeding may recur when the prostate cavity scabs fall off about 1 week or 2 weeks after the TURP operation. The standard initial hemostasis method currently used to treat post-TURP bleeding is to use a balloon catheter for manual traction, followed by continuous bladder flushing with saline. Typically, in the case of persistent bleeding, balloon pressure can be applied for up to 24 hours. If the bleeding is still uncontrollable after conservative treatment, the patient may have to return to the surgical operating room immediately to stop the bleeding by open or endoscopic surgery.
[0011] Despite advances in hemostasis using advanced dressing applications outside of GIB or TURP hemostasis, none of these advances translate to the unique circumstances of the gastrointestinal tract or bladder, particularly the upper GI tract, which are highly challenging in terms of delivery, adhesion, enzyme activity, persistent oozing, acidity, and urine-related considerations. Rapid hemostasis in TURP, open prostatectomy, and cystectomy is highly desirable.
[0012] Gastrointestinal bleeding (GIB) is a common presentation to the emergency department. According to the U.S. Department of Health and Human Service, an average of more than 350,000 hospital discharges were due to GI bleeding each year from 2000 to 2014. In the United States, direct hospital costs due to GIB exceeded $1.1 billion in 2010 [1]. Upper GIB (UGIB), defined as bleeding in the gastrointestinal tract near the ligament of Treitz, is approximately five times more common than lower GIB (LGIB) [2]. Acute UGIB is a potentially life-threatening emergency that requires rapid evaluation, resuscitation, and appropriate medical and endoscopic management. Despite recent advances in the management of GIB in Western countries, the mortality rate of acute UGIB has not improved significantly and remains high at 10-14% [3,4]. The major cause of death after GIB is death secondary to cardiopulmonary complications, which is not surprising given the burden of comorbidities in such patients; death due to uncontrolled bleeding has been reported in 20%–25% of cases.[5,6] Although there are few options for acute correction of comorbidities, more effective and rapid hemostasis would significantly reduce the incidence of UGIB-related morbidity and mortality. In general, the most common causes of acute UGIB are ulcer disease, gastroesophageal varices, Mallory-Weiss tears, and erosive esophagogastritis.[7] Nonvariceal upper gastrointestinal bleeding (NVUGIB) encompasses all causes of UGIB other than esophageal bleeding or gastric varices. The incidence of peptic ulcer disease has decreased due to the development and use of proton pump inhibitors and the identification, treatment, and eradication of Helicobacter pylori in individual patients.[8] Despite the decrease in the incidence of peptid ulcers, the mortality rate among patients with NVUGIB is 3–4%.[9] Although rarely life-threatening, gastric malignancies can cause diffuse bleeding in fragile tissues that is difficult to resolve with traditional physical hemostasis methods (clips, bandages, ligatures) or cauterization
[10] .
[0013] Current endoscopic management of patients with acute UGIB includes thermal therapy (e.g., bipolar electrocoagulation, heater probe, monopolar electrocoagulation, argon plasma coagulation, and laser), injections (epinephrine, sclerosants (e.g., anhydrous ethanol, polyethylene glycol monolauryl, and ethanolamine)), thrombin or fibrin glue (thrombin + fibrinogen)), and clips [11,12].
[0014] Typically, in most patients with peptic ulcer bleeding, a combination of the above endoscopic treatment approaches can achieve hemostasis. However, there remains a subset of patients (approximately 5%) in whom endoscopic treatment is insufficient to achieve hemostasis and who therefore require interventional radiology or surgical intervention [13,14].
[0015] Endoscopic therapy has failed for a variety of reasons, including poor visibility of the lesion due to active, pulsatile bleeding, difficulty in endoscopically determining the anatomical location of the lesion, maximal treatment with currently available tools, and severe coagulopathy. Only three different spray-based hemostatic powder devices have been considered for use outside the United States: Ankeford Blood Stopper
[15] , EndoClot TM
[16] and HemoSpray TM [17-19] to control NVUGIB. A potential problem with Hemospray is that it is WoundStat TM A related product was withdrawn from the United States in 2009 because its procoagulant nanoparticle bentonite promoted diffuse microemboli
[20] , which could lead to tissue necrosis and organ failure.
[0016] Benign prostatic hyperplasia (BPH) and prostate cancer are the two most common urological conditions treated surgically in older men. It is estimated that by age 50, 50% of men have histologic evidence of BPH, and by age 80, 75% of men are thought to exhibit histologic evidence of BPH. In 40-50% of these patients, BPH is clinically significant. Although the incidence of uncontrolled bleeding from surgical procedures involving the prostate and urethra is relatively low, there is still a significant risk that they must be hospitalized for at least two to three nights to resolve. According to a statistical analysis from the U.S. Department of Health and Human Services from 2005 to 2010, an average of 150,000 men were discharged from the hospital after prostatectomy via open or transurethral surgery, with direct surgical costs averaging more than $4.5 billion per year. Among these patients, the average length of stay for open or transurethral prostatectomy was 3.1 days and 2.4 days, respectively. Patients who required a blood transfusion during surgery due to significant blood loss (4-5%) had an average hospital stay extended to five or six days, costing an average of $15,700 more per case compared to the average cost of a prostatectomy patient ($29,300) in 2010. Prostatectomy is more expensive due to operating room time, surgeon time, and hospital stay.
[0017] TURP is considered the benchmark treatment for BPH. Partial removal (resection) of the prostate gland is performed in TURP through minimally invasive surgery and electrocautery using a cystoscope (an endoscope passed through the urethra for the bladder). The fine loop electrocautery used in TURP reduces tissue necrosis compared to other less common minimally invasive prostatectomies, however, bleeding is more common during surgery with TURP. Like other forms of prostatectomy, proper control of bleeding during prostatectomy and TURP is a major challenge. The amount of intraoperative bleeding during prostatectomy depends on the size of the prostate, the length of time the prostate is removed, and the skill of the surgeon. Significant or heavy bleeding after prostatectomy often causes undesirable blood clots to be retained in the bladder and urethra (and result in urinary retention), which may prolong hospital stays or even necessitate a repeat operation. Arterial bleeding is usually easily identified and controlled with electrocoagulation, but venous bleeding, which is common in TURP, is more difficult to control. Attempts to control venous bleeding with electrocautery and irrigation may result in adverse consequences, such as TURP syndrome. In the standard of care, venous bleeding is controlled by filling the bladder with perfusion fluid and applying an inflated transurethral balloon catheter to compress the bleeding prostatic cavity. Postoperative morbidity associated with TURP has been reported to be as high as 18%, with an operative mortality rate of 0.3%. In elderly patients, the risk of morbidity and mortality related to blood loss is significantly increased in association with coagulopathy and cardiovascular abnormalities. Uncontrolled bleeding during TURP remains one of the major complications of prostatectomy, and this often leads to conversion to a less optimal open surgery. Despite significant advances in the management of BPH, the incidence of uncontrolled massive bleeding remains around 6%, and the transfusion rate to resolve this bleeding is 4%-5%.
[0018] In a typical TURP, the hospital stay is 2 to 4 days, and the patient has an inflated balloon catheter in place until the bleeding stops and the urine becomes clear. Any significant reduction in postoperative bleeding after TURP will shorten the catheterization time and bed requirements. It will also reduce the incidence of urinary tract infections, catheter-related patient discomfort and related complications. Large amounts of hematuria (blood in the urine) caused by transurethral or open surgery can cause hemodynamic instability and thrombus retention, which requires immediate medical attention and medical care for hemostasis, clot removal, blood transfusion and coagulation evaluation. Treatment of severe hematuria by transurethral approach is cumbersome due to limited surgical vision and space constraints. In most cases, patients must return to the operating room for open bladder surgery to achieve hemostasis and remove cystic blood clots. A complicating factor of prostatectomy is that TURP patients often require anticoagulation due to the presence of other chronic conditions, such as cardiovascular disease. Although it is preferred that these patients take anticoagulant medications such as Coumadin and Plavix prior to TURP surgery because of the risk of bleeding, it is preferred that the surgery be performed while the patient continues on the medication to reduce the occurrence of stroke or myocardial infarction during surgery. There is a pressing need for a reliable and sustainable hemostatic technique for transurethral administration to control post-prostatectomy hemorrhage, preferably effective in anticoagulated individuals.
[0019] Chitosan materials have been used in the art to address bleeding problems in various applications with varying degrees of success, but improvements and refinements are urgently needed to unlock the potential of catechol-modified chitosan to provide alternative and better chitosan-based solutions for safe, reliable and effective delivery of bioactive chitosan materials in vivo and particularly in challenging in vivo biological environments.
[0020] Brief summary
[0021] The present invention relates to tissue-adherent chitosan materials that resist dissolution. These chitosan materials comprise catechol-modified chitosan and are generally referred to herein as "dressings," a term used to refer to solid dry materials formed from the chitosan materials of the present invention. The chitosan materials may be suitable and applicable for minimally invasive procedures.
[0022] It should be understood that the chitosan materials described herein have many beneficial properties derived from the chitosan materials themselves, and these chitosan polymaterials can take a variety of potential solid forms. The beneficial properties derived from and characterized by the chitosan materials described herein include, but are not limited to, the ability to adjust the material by controlling the degree of substitution and oxidation level. By adjusting the material by controlling the degree of substitution and oxidation, the chitosan material can resist rapid degradation in difficult biological environments, such as the gastrointestinal tract, urethra, lower digestive tract, body cavities, such as the abdominal cavity and thoracic cavity, but still sufficiently soluble and can disappear in less than seven (7) days. Other beneficial properties of the chitosan material are that it also has biocompatibility, hemostasis and tissue adhesion. In addition, the solid dry chitosan material described herein can be provided in a final form or a discrete dry material configuration, which may displace interfering fluids due to its capillary action (pores or porosity) and / or applied pressure, in some cases, the pressure should be lighter (e.g., about 1 atm), and in the case of dry powder, it should be delivered under inflation pressure. The chitosan materials of the present invention are produced in final form or discrete dry material configurations that provide rapid adhesion and resist dissolution.
[0023] The dressings described herein are provided as non-limiting example final forms made using the chitosan materials of the present invention. The dressings described and exemplified herein provide examples of converting catechol-modified chitosan materials into various test articles or final forms that exhibit the solid properties of solid chitosan materials. Further final forms of dry solid chitosan include, but are not limited to, frozen phase-separated matrices and dressings formed therefrom, fibers, powders, films, membranes, meshes, pleglets, and the like. The present disclosure generally relates to chitosan dressings that, given their properties, can be applied in different physiological environments for hemostasis. Embodiments include chitosan gastrointestinal hemostatic dressings (CGHD) and chitosan intraluminal hemostatic dressings (CEHD), and the like.
[0024] The materials of the present invention have a combination of one or more or all of the following properties: (1) can be compacted for delivery without tearing or loss of mechanical properties; (2) can be applied in the presence of blood and other biological fluids at about 37°C without significant change in length, width and height dimensions or loss of mechanical properties; (3) can be delivered in the presence of biological fluids and blood; (4) can be delivered to the surgical site manually or by a minimally invasive delivery device; (5) can expand from a compacted state at the delivery site; (6) can undergo capillary action to achieve porosity and absorbency that can remove hydrophilic and hydrophobic biological fluids that would interfere with adhesion; (7) can be applied under uniform pressure to achieve a certain degree of adhesion. (8) when dry, is capable of contacting itself and the packaging material without adhering to itself or the packaging; (9) comprises at least one tissue-adherent side of a material which, when wetted by urine or blood, is capable of contacting itself or the packaging or delivery material without adhering to itself or the packaging or delivery material if the wet contact does not exceed 300 seconds; (10) is capable of uniformly adhering to tissue and rapidly promoting local clot formation; (11) is capable of being released from a delivery device to allow the delivery device to be withdrawn from the surgical site; and (12) is capable of maintaining a temperature of about 37°C and a pH of about 10°C for the first 12 hours of administration. (13) capable of resisting dissolution upon exposure to biological fluids in the range of pH 3.0 to about pH 8; (14) capable of utilizing (with or without a delivery device in place) ostomy access passages, such as those in the gastrointestinal tract and the urinary tract to maintain patency of materials or material residues present in the patent and of passage of excretion; (15) protecting the site of injury and providing promotion of healing; (16) providing controlled slow degradation and / or dissolution from the site of attachment to allow removal without surgical assistance in less than seven days after ostomy use; (17) the material of the present invention may include, but is not limited to, adhesive dressings, adhesive hemostatic dressings, internal adhesive fixatives, adhesive patches for local controlled release of active agents, sutures, staples, orthopedic bone fixators, occlusive suture-less patches, and materials that promote coagulation and seal vascular malformations.
[0025] Although existing tools in the United States readily control a significant portion of UGIB, there remains an unmet need for a low-risk device of the subject invention that can rapidly control fast-moving arterial bleeding. Widespread use of the subject invention would be able to significantly reduce morbidity and mortality in the treatment of gastrointestinal bleeding while reducing associated healthcare costs.
[0026] The chitosan material of the subject invention is suitable for use in all gastrointestinal bleeding applications and can be delivered, for example, through a standard endoscope working channel (≤3.2 mm diameter) or through a balloon catheter as a chitosan gastrointestinal hemostatic dressing (CGHD). The subject material of the present invention will provide an opportunity to address or reduce the deficiencies of current modalities such as shearing, thermocoagulation, and injection, which require high precision and are challenging when visibility is compromised in faster bleeding conditions.
[0027] The present invention includes compositions, methods of using the compositions, and methods of making the compositions.
[0028] In a preferred embodiment, the chitosan material comprises catechol-modified chitosan, wherein the CGHD dressing formed from the material has hemostatic function and has a thickness of 500 microns or less. The CGHD dressing may have a dry dressing thickness of one of: (i) about 200 microns or less; (ii) about 100 microns or less; or (iii) about 50 microns or less. The dressing may have a dry dressing thickness of about 0.03 g / cm 3 - About 0.7g / cm 3 The density of the following ranges: (i) about 0.3 g / cm 3 - About 0.4g / cm 3 (ii) about 0.4 g / cm 3 -About 0.5g / cm 3 ; or about 0.35g / cm 3 - About 0.55g / cm 3. The dressing can be compressed. The dressing can be square, rectangular, circular, or annular petal-shaped, and for each of the length and width of the square or rectangle, the measurement can be between about 10 mm and about 50 mm, or for the circular or annular petal-shaped, the diameter measurement can be between about 10 mm and about 50 mm. In certain embodiments, the dressing measures one of the following: (i) 10 mm×10 mm; (ii) 20 mm×20 mm; or (iii) 25 mm×25 mm. The dressing has a moisture content when dry: (1) 15% or less by weight (w / w); (2) 8% or less by weight (w / w); or (3) 4% or less by weight (w / w). The dressing can have an adhesive side and a non-adhesive side. The dressing can have an adhesive side disposed on a first layer and a non-adhesive side disposed on a second layer. When the dressing is wet, the adhesive side of the dressing will adhere to the tissue surface. When the dressing is wet, the non-adhesive side of the dressing will not adhere to the delivery device. The dressing may adhere to the gastrointestinal mucosa in 1 minute or less. The dressing may form a quaternary ammonium cation on the chitosan glucosamine C-2 amine at the tissue site. The dressing may include catechol oxidized to o-quinone and cross-linked in the chitosan dressing. The chitosan dressing may have a brown coloration, including a dark brown coloration. In one embodiment, the dressing may include unoxidized catechol, and wherein the chitosan dressing has a pink coloration. The dressing may include a freeze-dried layer. The dressing may include a freeze-dried structure having a thickness of 50 microns or less. The dressing may include a freeze-dried structure including more than one freeze-dried layer. The dressing may include spun fibers. The dressing may include a porous surface. The dressing may include a porous surface, wherein the porous surface provides one or more of: (i) and an absorbent surface; and (ii) a channel that redirects moisture away from the target tissue surface site. When in a wet state, the dressing may adhere to wet tissue. The adhesive strength of the dressing may be greater than or equal to about 1 kPa. The dressing resists dissolution in water, saline solution, blood or GI fluid at about 37°C for at least about 6 hours. The dressing may be folded or rolled up without rupture or tearing. The dressing has an outwardly facing surface area in an open, unfolded or unfolded state that is about six times, about five times or about four times the outwardly facing surface area of the same dressing in a closed, rolled up or folded state. The dressing may have an outwardly facing surface area ratio of about 15:1, or about 14:1, or about 13:1, or about 12:1, or about 11:1, or about 10:1, or about 9:1, or about 8:1, or about 7:1, or about 6:1, or about 5:1, or about 4:1, or about 3:1, or about 2:1 in an open, unfolded or unfolded state relative to a closed, rolled up or folded state. The dressing may be pierced or sutured without rupture or tearing. The dressing may be cross-linked.The dressing can be delivered intact by a balloon device, a wire device, or an endoscopic device, wherein the device can include a working channel having a diameter of 3.2 mm or less, and wherein the dressing is delivered through the working channel. By applying a light pressure, such as about 200-300 g, the dressing can wet and completely adhere to the gastric mucosa in less than 30 seconds. The dressing can remove hydrophilic and hydrophobic biological fluids that interfere with adhesion. The dressing can remain in place intact and stop moderate bleeding of about 20 ml / min-about 150 ml / min. After adhering to the target tissue site, the dressing is easily detached from the delivery device. In an acidic environment of corrosive enzymes and about pH 3, after being attached to the injury site, the dressing can resist dissolution for at least six hours. The dressing can seal and protect the target tissue site for at least 12 hours. The dressing can achieve controlled slow dissolution from the attachment site within a time limit of no more than seven (7) days. The dressing can be folded and unfolded. The dressing can be rolled up and unfolded. The dressing is not readily soluble in water, saline solution, blood, or GI fluid at about 37°C for at least 12 hours after application. The dressing is not readily soluble in water, saline solution, blood, or gastrointestinal fluid at about 37°C for at least 24 hours after application. The dressing does not adhere to the delivery device. The dimensions of the dressing do not increase or decrease by more than about 25% in length and width and by more than about 50% in thickness dimension in the presence of water, saline solution, blood, or GI fluid at about 37°C. The dressing comprises an adhesive side that interacts with the site of injury, and the chitosan dressing comprises a non-adhesive side that interacts with one of the delivery devices or the adhesive side when in a dry and folded or dry and unfolded state. The dressing is capable of terminal sterilization without affecting the properties of the dressing. The chitosan dressing is capable of being stored over time under controlled conditions without affecting the properties of the dressing.
[0029] The range of UGIB excretion rate or blood flow rate expressed in ml / min suitable for treatment by the device described herein can be about 1 ml / min-about 200 ml / min. In a preferred embodiment, the bleeding rate solved by the device is about 1 ml / min-about 150 ml / min. Forrest 1a UGIB is about 25 ml / min. For subjects with bleeding rates much higher than Forrest 1a, unless they are already in the operating room, the possibility of survival is not great. UGIB bleeding rates of about 20 ml / min-25 ml / min are considered "fast" bleeding. Oozing is usually greater than about 1 ml / min, because it is noted that low bleeding rates such as 1 ml / min typically coagulate and stop on their own, unless the subject is receiving anticoagulant therapy or suffers from a coagulation cascade disease for some reason, excluding taking anticoagulant drugs. For subjects using irreversible anticoagulants or having bleeding disorders, oozing of 1 ml / min remains a concern and needs to be solved by a device formed by the material of the present invention. In some embodiments, the device described herein is used to address the bleeding rate of UGIB at about 1 ml / min to about 25 ml / min, or about 1 ml / min to about 20 ml / min, or about 1 ml / min to about 15 ml / min, or about 1 ml / min to about 10 ml / min, or about 1 ml / min to about 5 ml / min. In some embodiments, the dressing can be used to treat a disease, condition, disorder, wound, or injury. For example, the use of the dressing in treating a disease, condition, disorder, wound, or injury includes directly adhering the dressing to the injury site when wetted, and applying pressure to the dressing for about 30 seconds. The dressing for treating a disease, condition, disorder, wound, or injury can remove hydrophilic and hydrophobic biological fluids when adhered. The dressing for treating a disease, condition, disorder, wound, or injury can include leaving the dressing in place at the target tissue site, and the dressing can be retained at the target tissue site for at least 24 hours. The dressing for treating a disease, condition, disorder, wound, or injury can slowly dissolve at the target tissue site and completely dissolve without human intervention within 7 days or less.
[0030] In some embodiments, the invention disclosed herein comprises a method for producing a chitosan dressing. In one embodiment, the method comprises: synthesizing with chitosan and catechol in an aqueous reaction solution; maintaining the pH of the reaction solution at pH 5.5 or below; increasing the pH of the reaction solution; and exposing oxygen to the reaction solution to provide oxidation and crosslinking of the catechol; and drying the reaction solution. In certain embodiments, the method does not comprise an intermediate drying step between the steps. In certain embodiments, the method comprises increasing the pH of the reaction solution from about 5.8 to about 6.2. Another embodiment of the method for producing a chitosan dressing comprises a method for producing a chitosan dressing, the method comprising: freeze drying a first aqueous solution comprising chitosan; freeze drying a second aqueous solution comprising chitosan; obtaining a low-density chitosan dressing having an interconnected porous structure through the above steps; and compressing the low-density chitosan dressing from each step; and preparing a two-layer chitosan dressing from the compressed low-density chitosan dressing. In certain embodiments, the low density chitosan dressings from each of the freeze drying steps described above are combined together prior to compression. In certain embodiments, the compression step can occur at a temperature in the range of about 20° C. to about 150° C. In certain embodiments, the dressing is dried to a moisture content of less than about 15% (w / w).
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. Methods and materials for use in the present invention are described herein; other suitable methods and materials known in the art may also be used. The materials, methods, and examples are exemplary only and are not intended to be limiting. All publications, patent applications, patents, sequences, database entries, and other references mentioned herein are incorporated herein by reference in their entirety. In the event of a conflict, the present specification, including definitions, shall prevail.
[0032] Other features and advantages of the invention will be apparent from the following detailed description and drawings, and from the claims.
[0033] Brief description of the multiple viewing angles of the attached drawings
[0034] Figure 1A , 1B , 1C, 1D, 1E, 1F and 1G describe the introduction, placement and application of dressings formed from the materials of the present invention.
[0035] Figure 2A digital image depicting a folded, double-sided dressing formed from the material of the present invention held in gloved hands, wherein the darker side is the tissue adhesive catechol-modified chitosan side and the lighter side and other edge areas are the unmodified chitosan dressing side (the surface diameter of the unmodified dressing is 2.5 inches, while the surface diameter of the modified catechol dressing is 2 inches).
[0036] Figure 3A and Figure 3B Digital image depicting a double-sided catechol-modified chitosan dressing formed from the material of the present invention adhered to the wall of a 250 ml volumetric flask at approximately 48 hours after initial attachment, applied via a balloon catheter at 25±3°C for 2 hours and immersed in a 0.9% w / w physiological aqueous solution. Note that there is no trace of the original unmodified chitosan dressing at 48 hours. Figure 3A is a side view, Figure 3B It is a floor plan.
[0037] Figure 4 A digital endoscopic image depicting a catechol chitosan dressing formed of the material of the present invention uniformly adhered to the bladder neck and urethral lumen of an approximately 100 pound female pig within 30 minutes. The bladder was swollen with injection of urine and saline to aid in visualization. The image was obtained by delivery through an endoscopic trocar through the pig bladder wall and using the endoscopic viewport to aim at the pig bladder neck and into the urethra. The image shows a distinct non-healing, sparse, rapidly degrading unmodified chitosan lining and a modified catechol dressing that adhered tightly to the bladder neck and lumen of the urethra.
[0038] Figure 5A and 5BOne image depicting a folded dressing in plan view, all other images are cross-sections / sides. Reference numerals (if included in the drawing) correspond to the following written text: 1-prostate; 2-bladder; 3-urethral mucosa; 4-catheter barrel; 5-sheath; 6-rolled CEHD on delivery balloon of delivery catheter; 7a-conical folded CEHD with connection point (14) located proximal to delivery balloon catheter (left); 7b-conical folded CEHD with connection point (14) located distal to delivery balloon catheter (right); 7c-plan view of conical folded CEHD with connection point (14) distal. Note that there may be two dressings on one balloon, with distal and proximal connections, or only one dressing, with only a proximal connection. An alternative delivery method for the CEHD is to roll it up into a cylinder around the delivery balloon, but this is not shown; 8-delivery balloon (there are images of a single balloon catheter (less preferred) and a dual balloon (preferred)). In a dual balloon catheter, the delivery balloon is also the proximal balloon; 9-cut to create a circular window connection point toward the apex of the conical folded dressing (proximal 9a; distal 9b); 10-overlapping edges of the two faces of the conical dressing facing each other; 11-top of the conical folded CEHD (11a proximal; 11b distal); 12-irrigation port (12a proximal; 12b distal); 14-connection point of the conical folded CEHD apex to the balloon catheter, where the body of the CEHD is folded and rolled around the delivery balloon. A simple double-sided pressure adhesive works well to secure the CEHD apex to the catheter. This connection helps the snug-fitting sheath slide over the folded and rolled CEHD without the CEHD getting caught in the sheath during use; 15-distal or placement / positioning of the balloon in a dual balloon delivery catheter. This is preferred over a single balloon catheter because the distal balloon can be used to rupture and initiate removal of the sheath and provides the ability to ideally position the delivery balloon. In the case of anastomosis and bladder neck injury, the distal balloon can be used to achieve CEHD apposition to the bladder neck; and ports for the 16-balloon catheter (typically 3 ports in a 2-balloon catheter, however, a multi-lumen catheter with 2 balloons may have more). Typically, there is one port per balloon, and at least one point for irrigation and drainage. These ports typically connect to standard syringe luer adapters.
[0039] Figure 6 Chemical structure representations depicting chitosan (R1 = H and acetyl) and catechol-modified chitosan (R1 = H, acetyl, hydrogenated caffeic acid residues, caffeic acid residues, trans-caffeic acid residues and plateau catechin residues). For chitosan polymers, preferably n>60, more preferably n>300, and most preferably n>600.
[0040] Figure 7An N-acylation addition reaction in the presence of 1-ethyl-3-(-3-dimethylamino-propyl)-carbodiimide is described, wherein 3,4-dihydroxyhydrocinnamic acid is covalently linked to the chitosan C-2 amine at a degree of substitution of 25% in aqueous solution at pH 5.5.
[0041] Figure 8 The oxidation of catechol-modified chitosan to o-quinone-modified chitosan at elevated pH and in the presence of oxygen is described.
[0042] Fig. 9 Depicted are the Schiff base (A) and Michael addition (B) reactions leading to cross-linking between catechol-modified chitosan and chitosan.
[0043] Fig.10 A 4 cm long, 1.5 cm inner diameter glass flow cell is described which is ligated by wrapping both ends of the cell and applying pressure to a 6 cm long, 1.5 cm diameter stretch tube capable of supporting porcine small intestinal submucosa.
[0044] Fig.11 Describes a typical flow cell design (3 cells connected in parallel) used to test the adhesion and dissolution resistance of a novel dressing to a cell-supported ex vivo tissue surface in a stream of urine at 37°C.
[0045] Figures 12A-12G Table showing different parameters used to prepare batches of chitosan dressings.
[0046] Figures 13A-13E Table showing different chitosan dressing formulations including formulation, solubility, foldability, burst testing, ex vivo, accelerated stability, and in vivo properties.
[0047] Fig.14 Circular catechol-modified chitosan dressings are depicted that are (pre-cut) 2.5 inch by 2 inch diameter and compressed to a shape close to 50 microns. The coloration of these catechol-modified chitosan dressings ranges from left to right from a light pinkish brown (first dressing), 2 darker pinkish brown dressings, 2 tan dressings (no pink), 1 brown dressing, and the last 1 dark brown dressing. Catechol chitosan dressings 5 and 6 were formed from 2.5 inch and 2 inch molds, and they were backed from the 2.5 inch mold with an unmodified chitosan dressing, respectively, and the unmodified chitosan can be clearly observed as a white halo (no brown or pink) in dressing 6. During the compression process, the catechol chitosan and unmodified chitosan dressings were bonded to each other to a final shared density of >0.4 g / cm 3The pink coloration is associated with unoxidized catechol, while the brown coloration is associated with oxidized catechol (o-quinone). The lighter brown and lighter pink colors are associated with lower degrees of substitution of chitosan with catechol (close to 10%), while the darker colorations (pink-brown and brown) are associated with higher degrees of substitution of chitosan with catechol (close to 20%).
[0048] Fig.15 A catechol-modified chitosan dressing is described which has been folded and unfolded while remaining intact and having a visible fold axis (crease).
[0049] Figures 16A-16C Description Table showing dissolution test results.
[0050] Figures 17A-17C Describes a table showing the formulation method, hydrophilic polymer and % w / w of the hydrophilic polymer components of the solution.
[0051] Fig.18 Gastroscopic digital images depicting the modified catechol chitosan dressing of the present invention that adheres tightly to the gastric mucosa, showing mild swelling in the gastric environment, and effectively controlling upper gastrointestinal bleeding from a lacerated gastroepiploic artery inside the stomach of a heparinized (ACT ≥ 250s) pig 3 hours after application of the dressing to the arterial injury (Forrest 1a).
[0052] Fig.19 Shown when the animal was killed Fig.18 There is a complete strong clot under the dressing, and the clot is photographed in the Fig.18 The modified chitosan dressing was confirmed to be uniformly adhered to the lesion and gastric mucosa at the time of sacrifice.
[0053] Figure 20-25 An experiment is described which involves a circulating peristaltic pumping system of 0.9% saline through a 15 mm diameter glass pool containing the lumen of the porcine small intestinal submucosa at a flow rate of 20 ml / min for 163 hours (approximately 7 days-168 hours) with a system temperature of approximately 27°C. A small 10 mm x 10 mm patch of the modified catechol chitosan material of the present invention was attached to the surface of the small intestinal submucosa in the glass pool by hand and observed over time. The images showed that the material remained firmly adhered to the lumen of the submucosa for 7 days without any loss of adhesion. On the 7th day and the lumen was removed from the pool, it was found that the material had degraded and became very fragile. The system was used to screen formulations for transurethral administration. In this model, unmodified chitosan lasted less than 2-3 hours.
[0054] Fig.26Gastroscopic digital images depicting a modified catechol chitosan dressing formed from the inventive material of the present invention that adheres tightly to the gastric mucosa, showing mild swelling in the gastric environment, and effectively controlling upper gastrointestinal bleeding from a torn gastroepiploic artery inside the stomach of a heparinized (ACT ≥ 250s) pig 3 hours after application of the dressing to the arterial injury (Forrest 1a).
[0055] Detailed Description
[0056] In one aspect, the present invention relates to a biocompatible, foldable, thin, chitosan-based dressing comprising catechol-modified chitosan and characterized by one or more or all of the following features such that it: (1) is capable of being delivered intact by balloon or by endoscopic device; (2) is capable of wet and adhere intact to the gastric mucosa within 30 seconds under the application of gentle pressure; (3) has capillary action, porosity and absorbency that can remove hydrophilic and hydrophobic biological fluids that would interfere with adhesion; (4) is capable of staying in place and stopping moderate bleeding, such as bleeding rates of about 20 ml / m in-about 100 ml / min or more; (5) capable of being released from a delivery device to allow the delivery device to be withdrawn from the GI environment; (6) capable of resisting harmful rapid decomposition (<6 hours) by corrosive enzymes and acidity (≥pH 3) in the GI environment; (7) capable of protecting the gastrointestinal injury site preferably for up to 12 hours, more preferably for up to 24 hours, and most preferably for up to 96 hours to assist in its subsequent acute healing and closure; and (8) capable of achieving controlled slow dissolution from the attachment site so that it can be completely removed without assistance in less than 7 days, with the dissolved residue safely passing through the digestive tract.
[0057] The present invention addresses the problem of rapid hemostasis during transurethral prostatectomy, open prostatectomy, and cystectomy using a foldable, thin (thickness ≤ about 500 microns), tissue-adhesive, chitosan-based hemostatic dressing. The dressing formed from the material of the present invention has one or more or all of the following characteristics, making it: (1) capable of being folded or unfolded, unfolded and unfolded without tearing or compromising mechanical properties; (2) capable of being applied at about 37°C in the presence of blood and urine without significant changes in the length, width, and height dimensions or loss of mechanical properties; (3) capable of being delivered in the presence of urine and blood; (4) capable of being delivered to the site of injury via an intracavitary or transurethral delivery device; (5) capable of being unfolded or unfolded at the delivery site; (6) characterized by capillary action, porosity, and absorbency, which can remove hydrophilic and hydrophobic biological fluids that would interfere with adhesion; and (7) capable of adhering to the bladder mucosa, excised bladder mucosa, and excised prostate by wetting under the application of uniform pressure. activation; (8) when dry, capable of contacting itself and the packaging material without adhering to itself or the packaging; 9) comprising a tissue adhesive side of the dressing which, if in contact with moisture for no more than about 300 seconds, is capable of contacting itself or the packaging or delivery material when wetted by urine or blood without adhering to itself, or the packaging or delivery material; (10) capable of uniformly adhering to tissue and rapidly stopping moderate oozing bleeding, e.g., bleeding rates of about 20 ml / min to about 100 ml / min or more, at pressures of ≤ about 50 mmHg, affording the opportunity for TURP to be performed as an outpatient procedure; (11) capable of being released from a delivery device to permit withdrawal of the delivery device from the urethra; (12) capable of being resistant to urethral bleeding within the first 12 hours of application at a pH of about 4.5 - about pH 8 resists dissolution when exposed to urine at about 37°C; (13) maintains the urethra (with or without a delivery device in place) in an open state, with or without the presence of a dressing or dressing residue, and permits unimpeded passage of urine; (14) protects the site of injury and provides for promotion of healing; (15) provides controlled, slow degradation and / or dissolution from the site of attachment (bladder neck, prostate and / or urethra) to allow removal without surgical assistance in less than about 7 days.
[0058] The present invention provides: (1) the ability to rapidly control bleeding during prostatectomy using a non-invasive procedure; (2) the ability to control bleeding in anticoagulated patients; (3) significantly reduced pain and discomfort for patients by controlling bleeding without the need for prolonged catheterization; (4) significantly reduced length of hospital stay; (5) significantly reduced health care costs; (6) significantly reduced morbidity; and (7) results that tend toward reduced mortality.
[0059] As used herein, bladder mucosa is broadly defined to include any exposed tissue surface in the bladder, including any tissue surface exposed by surgery (e.g., surgery). Thus, bladder mucosa includes bladder mucosa naturally present in the bladder, excised bladder mucosa, excised prostate, and the like.
[0060] As used herein, chitosan intraluminal hemostatic dressing (CEHD) refers to a chitosan dressing that is hemostatic and can be used, for example, in the intraluminal area inside the bladder. CEHD is not limited by its application site and includes chitosan dressings that can be used anywhere in the human body, including, but not limited to, the bladder mucosa.
[0061] The bleeding rate or blood flow rate in ml / min suitable for treatment by device as described herein can be about 1ml / min-about 200ml / min. In a preferred embodiment, the bleeding rate solved by the device is about 1ml / min-about 150ml / min. The bleeding rate of about 20ml / min-25ml / min is considered as "fast" bleeding. Oozing bleeding is usually greater than about 1ml / min, because it is noted that low bleeding rates such as 1ml / min typically coagulate and stop on their own, unless the subject is receiving anticoagulant therapy or suffers from coagulation cascade disease for some reason, does not include taking anticoagulant drugs. For such subjects using irreversible anticoagulants or having bleeding disorders, 1ml / min of bleeding is still concerned, and needs to be solved, for example, by a device formed by the material of the present invention. In some embodiments, the devices described herein are used to address TURP bleeding rates of about 1 ml / min to about 25 ml / min, or about 1 ml / min to about 20 ml / min, or about 1 ml / min to about 15 ml / min, or about 1 ml / min to about 10 ml / min, or about 1 ml / min to about 5 ml / min.
[0062] A TURP delivery device may include any device used in, or in conjunction with, a TURP procedure.
[0063] Chitosan dressing
[0064] Chitosan dressings can refer to compositions comprising different amounts of chitosan. For example, the general contents, general chemical compositions and different forms of chitosan dressings are described in U.S. Pat. Nos. 7,820,872, 7,482,503, 7,371,403, 8,313,474, 7,897,832, 9,004,918, 8,920,514, 9,204,957, 8,741,335, 8,269,058, 9,205,170 and 10,086,105. Such chitosan dressings are used for hemostasis because of their chemical and physical properties as described above.
[0065] Chitosan preferably used comprises non-mammalian material poly[β-(1→4)-2-amino-2-deoxy-D-pyranose. Chitosan can be processed in a conventional manner from chitin obtained, for example, from animal crustacean shells. Chitosan can be biocompatible and biodegradable in vivo and can be decomposed into benign substances glucosamine. The catechol-modified chitosan used herein can include chitosan to which catechol is added.
[0066] Chitosan dressings can be dry or wet. If the moisture content in the chitosan dressing is less than about 15% by weight, preferably about 10% by weight, and more preferably about 5% by weight, the chitosan dressing is "dry". When the chitosan dressing is in contact with a water source (including water in the physiological environment and biological fluids or aqueous solutions), the "chitosan dressing" is "wet". For example, when the chitosan dressing described in the present disclosure is in contact with gastrointestinal fluids, urine or blood or the tissue surface of the gastrointestinal tract or bladder (bladder mucosa or GI mucosa), it will become wet. The chitosan dressing retained substantially in solid form absorbs, displaces, redirects or guides water / moisture in the physiological environment of the gastrointestinal tract or bladder mucosa in an amount sufficient to make the chitosan dressing adhere to the tissue surface. The adhered chitosan dressing can be used to seal the wound surface and slow down or prevent further bleeding.
[0067] In a preferred embodiment, the chitosan gastrointestinal hemostatic dressing (CGHD) or chitosan intraluminal hemostatic dressing (CEHD) formed from the material of the present invention preferably contains greater than or equal to 25% by weight of chitosan; more preferably greater than or equal to 50% by weight of chitosan, and most preferably greater than or equal to 75% by weight of chitosan. Chitosan is a general term used to describe a linear polysaccharide composed of glucosamine and N-acetylglucosamine residues linked by β-(1-4) glycosidic bonds (typically the number of glucosamines ≥ N-acetylglucosamine), and its composition is soluble in dilute acid aqueous solution (Roberts 1991). The chitosan family includes poly-β-(1-4)-N-acetyl-glucosamine and poly-β-(1-4)-N-glucosamine, in which the acetyl residue portion and its motif decoration (random or block) affect the chitosan chemistry. The C-2 amino group on the glucosamine ring in chitosan allows protonation and thereby renders chitosan soluble in water (pKa≈6.5) (Roberts 1991).Other hydrophilic polymers may be used, for example, guar gum, pectin, starch, and polyacrylic acid.
[0068] In a preferred embodiment of CGHD, the dressing formed from the material of the present invention is polymeric, thin (preferably the dry dressing has a thickness of about ≤500 microns, more preferably a thickness of about ≤200 microns, and most preferably a thickness of about ≤100 microns), flexible, porous, dry, biocompatible, tissue-adhesive, and hemostatic.
[0069] In a preferred embodiment of CEHD, the dressing formed from the material of the present invention is polymeric, thin (preferably a dry dressing thickness of about ≤500 microns, more preferably a thickness of about ≤200 microns or about ≤100 microns, and most preferably a thickness of about ≤150 microns), flexible, porous, dry, biocompatible, tissue-adhesive, and hemostatic.
[0070] In some embodiments, the dressing is about 100 microns thick and may be a bilayer dressing comprising two approximately 70 micron layers (one layer being adhesive and anti-solvent and the other being direct chitosan) with a total thickness approaching 150 microns when delivered.
[0071] The shape of the dressing is not limited, but preferably a square, rectangular, circular or annular petal dressing. In one embodiment, the maximum size can be about 50mm x 50mm square or 50mm diameter at most. In another embodiment, the dressing size can be about 45mm x 45mm square or 45mm diameter, 40mm x 40mm square or 40mm diameter, 35mm x35mm square or 35mm diameter, 30mm x 30mm square or 30mm diameter, 25mm x 25mm square or 25mm diameter, 15mm x 15mm square or 15mm diameter, 10mm x 10mm square or 10mm diameter, etc. In another embodiment, the diameter of each of the length and width can be about 10mm-about 50mm or about 10mm-about 50mm. As the size of the dressing becomes larger, they are increasingly subject to the delivery restrictions in the limited cavity.
[0072] In another preferred embodiment, the dressing is delivered by a balloon catheter, and the dressing has a diameter size of about 5cm or 7cm maximum. The balloon catheter preferably passes through the central aperture in the dressing (same as the catheter balloon diameter, usually about 4mm-about 7mm diameter, or the hole can be larger, for example, 12mm at most), and the dressing (dressing 30mm-70mm diameter) is adhered to the catheter (same as the catheter diameter) relative to the balloon by the small dressing sheet on either side of the hole. In some embodiments, the surface area change of the dressing under folding, rolling up or compacting state is about 1 / 8 of the surface area when the dressing is in an unfolded, unfolded or uncompressed state. Dressing as described herein can provide a larger dressing surface area in an open, unfolded or unfolded state. Alternatively, dressing as described herein can provide a small dressing surface in a closed, rolled up or folded state. The ability of the dressing to fold, roll up or close makes them more compact and can protect delivery, and reduces the possibility of prematurely wetting the dressing surface before being delivered to the target tissue treatment site.
[0073] In a preferred embodiment of the CGHD, the dressing has a thickness of about 50 microns, a diameter of about 2.5 cm, and a width of about 9.856 cm. 2 The open, unfolded or expanded outward-facing surface area of the dressing is about 2.07 cm within the 0.45 cm diameter gastroscope channel within the delivery device sheath (typical fluorinated ethylene propylene (FEP) delivery tube wall thickness is about 150 microns). 2 The outward-facing cylindrical surface area of 1.25 cm in a 1.25 cm long cylinder, or about 1.56 cm in a 0.32 cm diameter gastroscope channel. 2 ; or about 1.41 cm in diameter within a 0.28 cm diameter gastroscope channel 2 Thus, in one example, a dressing of the present invention may have an outward-facing surface area in an open, unfolded or expanded state that is about six (6) times, about five (5) times, or about four (4) times greater than the outward-facing surface area of the same dressing in its closed, rolled or folded state. In some embodiments, the ratio of the outward-facing surface area of the dressing of an open, unfolded or unfolded dressing to the outward-facing surface area of the dressing of a closed, rolled or folded state is about 15:1 or about 14:1 or about 13:1 or about 12:1 or about 11:1 or about 10:1 or about 9:1 or about 8:1 or about 7:1 or about 6:1 or about 5:1 or about 4:1 or about 3:1 or about 2:1.
[0074] In some CGHD embodiments, the most common gastroscope channel is 0.28 cm diameter (2.8 mm), so this is the most preferred size for dressing delivery. Alternatively, a more preferred size is 0.32 cm diameter, which is a standard gastroscope channel diameter, but lower than the 0.28 cm channel. Another preferred gastroscope channel diameter size is between 0.45 cm-0.32 cm, which is a more customized gastroscope channel size, and thus less common than the 0.32 or 0.28 cm gastroscope channel diameter sizes.
[0075] In a preferred embodiment of the CEHD, the dressing has a thickness of about 100 microns, a diameter of about 5.0 cm, and a width of about 38.66 cm. 2 On a balloon delivery device, a closed, rolled or folded dressing has approximately 5.09 cm on a 7 mm diameter catheter balloon. 2 Outward facing cylindrical surface area (in a 2.5 cm long cylinder) or approximately 14.0 cm on a 4 mm diameter catheter balloon with a 3.0 cm diameter dressing. 2 Opening and 1.85cm 2 Thus, in one example, the facing surface area of a dressing of the present invention in an open, unfolded or unfolded state is about eight (8) times greater than the facing surface area of the same dressing in a closed, rolled or folded state. In some embodiments, the ratio of the facing surface area of the open, unfolded or unfolded dressing to the facing surface area of the closed, rolled or folded dressing is about 15:1 or about 14:1 or about 13:1 or about 12:1 or about 11:1 or about 10:1 or about 9:1 or about 8:1 or about 7:1 or about 6:1 or about 5:1 or about 4:1 or about 3:1 or about 2:1.
[0076] In some CEHD embodiments, the most common catheter bulb used with the delivery device in TURP is a 0.4 cm balloon diameter (4.0 mm), and therefore, this is the optimal size for dressing delivery. Alternatively, a more preferred size is a 0.5 cm diameter, which is a standard catheter diameter for TURP delivery devices, but is less common than a 0.4 cm catheter. Another preferred catheter diameter size for a TURP delivery device is between 0.5 cm-0.7 cm, which is a more customized channel size, and therefore less common than a 0.4 or 0.5 cm catheter diameter size.
[0077] The dressings described herein are capable of being folded and unfolded at a temperature of about 37°C, preferably 6 hours before application, more preferably 12 hours before application, and most preferably 24 hours before application, and are readily soluble in blood or body fluids, such as GI fluid or urine, and completely degrade and / or dissolve upon contact with GI fluid or bladder fluid at about 37°C within about 7 days.
[0078] The dressing as described herein will not adhere to the delivery device and will not appreciably expand or contract in the presence of blood and body fluids (GI fluid, urine or bladder fluid or mixtures thereof) at a temperature of about 37°C, i.e., it will not increase or decrease by more than about 25% in its length and width dimensions, or by more than about 50% in its thickness dimension.
[0079] In a preferred embodiment, the dressing can be terminally sterilized without affecting the properties of the dressing. Its tissue adhesion properties, mechanical properties, solubility in GI or bladder fluids, swelling properties, and hemostatic properties are stable and do not change significantly over time (e.g., about ≤ 2 years) when stored in its packaging under controlled conditions at room temperature of about 21°C to about 25°C.
[0080] In a preferred embodiment, the dressing has a tissue adhesive side and a non-adhesive side. In this embodiment, the non-adhesive side can provide a surface that, when wet, easily slides off of itself and from any applicator or delivery device surface that applies pressure to the dressing within the lumen and / or the gastrointestinal tract or bladder.
[0081] A preferred embodiment of the dressing is that it is formed from a substantially dry chitosan composition having a water content of about ≤ 15% or about ≤ 8%. The dry chitosan composition is preferably formed using phase separation and drying of an aqueous solution of chitosan and water. The dry chitosan dressing is preferably formed in sheet form, which can be cut to size.
[0082] Preferred embodiments of the biocompatible, biosoluble, tissue-adherent chitosan dressings are able to resist dissolution in gastrointestinal (GI) fluids and blood for at least about 6 hours at about 37°C, are tissue-adherent, and include materials and material structures that promote resistance to rapid dissolution and degradation in the low pH and strong enzymatic digestive fluids of the upper gastrointestinal tract. This is a significant advantage of the chitosan dressings disclosed herein because the upper gastrointestinal tract has evolved to rapidly digest most organic materials, including chitosan, cellulose, and starch.
[0083] Preferred embodiments of the biocompatible, biosoluble, tissue-adherent chitosan dressings are able to resist dissolution in bladder fluid and blood for at least about 6 hours at about 37° C., are tissue-adherent, and include materials and material structures that promote resistance to rapid dissolution and degradation by bladder urine. This is a significant advantage of the chitosan dressings disclosed herein.
[0084] The chitosan dressing provided herein can be applied to mucus surfaces, such as GI or bladder, by light pressure or pressure of up to hundreds of KPa. As used herein, the light pressure applied to the dressing on the tissue surface refers to a pressure that makes the chitosan dressing adhere and maintain contact with the injury site without obvious deflection or movement of the tissue, thereby allowing the chitosan dressing to interact with its composition structure and characteristics to promote adhesion to the injury site to stop bleeding. In some embodiments, light pressure is about most preferably 10kPa or less, more preferably 25kPa or less, or preferably 50kPa or less (note 100g / cm2=9.8kPa) pressure. Typically, significant deflection will occur when a load higher than 100kPa is applied to soft tissues such as the stomach, so that it is impossible to apply pressure without applying a supporting back pressure. The elastic modulus of the exploration of the human stomach is provided in Saraf et al. 2007. Saraf, H. et al. Mechanicalproperties of soft human tissues under dynamic loading, J.OF BIOMECHANICS, 40(9), pp. 1960-1967(2007).
[0085] Production of Chitosan Dressing
[0086] Various methods and processes can be used to produce the chitosan dressing of the present invention. In some embodiments, the chitosan dressing can be formed by freezing phase separation and drying. In an optional embodiment, the dressing is formed by adding a foaming agent to provide a low-density foam after freezing and before drying. The process of freezing phase separation and then removing the frozen solvent by sublimation is called freeze drying. Frozen phase separation is a process of solidification from a dilute solution, in which the heat removal and the resulting temperature reduction by the surface of the container or mold that retains the dilute solution lead to local solid crystal nucleation of the pure solvent, and the subsequent propagation and growth of the pure solvent crystal. The result of the growth of pure solvent crystals in a dilute solution is that the solute diffuses from the growing crystal front, thereby solidifying at the gaps between the growing crystals. The frozen phase separation of a dilute polymer aqueous solution results in the formation of thin polymer layers alternately between thicker ice layers. The ice is removed by a method that does not destroy the polymer layer to obtain a low-density polymer dressing with an interconnected porous structure. For example, in one embodiment, the low-density polymer dressing can have a density of about 0.005g / cm 3 -About 0.05g / cm 3 Initial dressing density.
[0087] In an optional embodiment, the frozen phase-separated dressing is formed by freezing a diluted solution of the foam and then drying it. In an optional embodiment, a dressing is formed by extruding a nonwoven fiber spinning process, such as centrifugal spinning, electrostatic spinning or solvent fiber into a coagulation bath. In another alternative embodiment, the dry dressing formed by the material of the present invention can be formed by a woven fiber process. In another alternative embodiment, the dry dressing formed by the material of the present invention can be formed by phase inversion and precipitation using a non-solvent (such as typically used to produce dialysis membranes and filter membranes). In another alternative embodiment, the dressing formed by the material of the present invention can be formed by an additive 3D printing method.
[0088] In a preferred embodiment formed from the material of the present invention, the dressing preparation process may include a compression process that reduces the initial dressing density from about 0.005 g / cm 3 -About 0.05g / cm 3 The initial preferred range is changed to about 0.03 g / cm 3 - About 0.7g / cm 3 The final preferred range; however, about 0.08 g / cm 3 -About 1.2g / cm 3 It should be noted that about 1.5 g / cm 3 The density is the density of a chitosan dressing without voids. The compression process may include applying a temperature of about 20°C to about 150°C. To avoid substantial expansion of the dry compressed dressing upon contact with biological fluids, the compression temperature is preferably applied by a method that may include, but is not limited to, convection, conduction, and radiation, and the temperature of the compressed dressing should preferably be maintained at least about 80°C for at least about 15 seconds.
[0089] Heat during compression is a tool that allows chitosan to be plasticized and formed without cracking or tearing the chitosan (non-destructive forming). The first glass transition temperature (Tg) of pure dry chitosan is close to 80°C, and if pure dry chitosan is processed close to this temperature, the chitosan will immediately undergo non-destructive forming and undergo a certain degree of crystallization annealing of its structure. By applying a plasticizer such as water or glycerol to the chitosan, the Tg can be lowered, thus providing a similar level of non-destructive forming at lower temperatures. In this article, it is noted that chitosan can be non-destructively formed in the range of 20°C-150°C. Outside this range, chitosan can still be molded non-destructively, but with greater difficulty. Above 150°C, chitosan begins to thermally degrade, while below 20°C, the addition of plasticizers may result in an undesirable loss of chitosan crystallinity, which provides resistance to dissolution and degradation processes such as those occurring during sterilization.
[0090] Preferably, compression prevents the dry compression dressing from expanding substantially upon contact with biological fluids and is performed with the moisture content of the dry dressing being approximately ≤ 15% w / w during compression.Compression may be applied by double or multiple rollers and / or uniaxially between adjacent compression plates.
[0091] The compression can be against a uniform flat or curved surface to provide a smooth finish to the compressed dressing.
[0092] Alternatively, compression may be applied to an etched, machined, ablated or other type of surface treatment, which imparts a depleted or increased surface texture. The surface texture may be random or may be a regular repeating pattern. The surface pattern may contribute to folding and unfolding the dressing, or may roll up and unfold the dressing, and may provide a hinge-like characteristic in the dressing. Such texture may be used as an aid to quickly lock the dressing in place and prevent its movement when applied. The movement of the dressing surface while facing the target tissue surface may cause film formation, and thus result in the closure of the open surface structure, thereby resulting in the loss of the ability to remove the surface anti-adhesive biological fluid, and thus the loss of the ability of the dressing adhesion surface. The time scale of changes on the dressing surface is very important, making the fluid absorption with obvious surface dressing channel closure very undesirable. A good way to avoid this movement is to immediately fix it physically once the dressing contacts the tissue surface.
[0093] Prior to the present invention, thin solid chitosan dressings were typically rigid, not flexible enough to bend or fold or roll up without breaking, rupturing, or otherwise losing their complete shape or otherwise being unsuitable. Due to its composition and properties, the chitosan dressings provided herein can be folded and unfolded along a folding axis while still intact and suitable for use in hemostasis. Significantly, and contrary to expectations, it has been found that the chitosan dressings described herein become less tolerant to tearing or breaking along the folded seams when folded. In some embodiments, due to its composition and properties, the chitosan dressings provided herein can be rolled up without losing its composition and properties, and still intact and capable of hemostasis.
[0094] In some embodiments of CGHD, due to its composition structure and characteristics, the chitosan dressing provided herein can be rolled up without losing the composition structure and characteristics, and still be intact and capable of hemostasis. Therefore, in some embodiments, the chitosan dressing provided herein can be delivered through a narrow working channel while still maintaining its composition structure and characteristics intact. Typical diameters of narrow working channels that may be delivered by the deacetylated chitosan dressings provided therewith include diameters of about 3.2 mm or less, and include, but are not limited to, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, and 3.2 mm.
[0095] In some embodiments of CEHD, due to its composition structure and characteristics, the chitosan dressing provided herein can be rolled up without losing its composition structure and characteristics, and still be intact and capable of hemostasis. Therefore, in some embodiments, the chitosan dressing provided herein can be delivered along the urethra by a balloon catheter while still keeping its composition structure and characteristics intact. Exemplary diameters of the balloon catheter supporting the chitosan dressing may include a diameter of about 12 mm or less, and include, but are not limited to 3 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm, 10.0 mm, 10.5 mm, 11.0 mm, 11.5 mm, and 12.0 mm.
[0096] Catechol-modified chitosan and its production
[0097] The chitosan dressing described herein relates to a chitosan dressing comprising catechol-modified chitosan and / or a hydrophilic polymer.Other aspects of the chitosan dressing comprising catechol-modified chitosan are described in more detail below.
[0098] Preferred embodiments of the CGHD or CEHD disclosed herein include compositions having catechol-modified chitosan and / or optionally other hydrophilic polymers. Preferably, the catechol-modified chitosan in the dressing provides long-term adhesion to moist tissue, wherein tissue adhesion is ≥ about 1 kPa, resists dissolution in water, saline solution, blood, and / or GI or bladder fluid for ≥ about 6 hours at about 37°C. Preferably, the catechol-modified chitosan is formed by N-acylation of the C-2 amine on the chitosan glucosamine with 3,4-dihydroxyhydrocinnamic acid (also known as 3-(3,4-dihydroxyphenyl)propionic acid, hydrogenated caffeic acid). Alternatively, chitosan is N-acylated to produce catechol-modified chitosan including, but not limited to, modification with one of 3,4-dihydroxycinnamic acid (caffeic acid); trans-3,4-dihydroxycinnamic acid (trans-caffeic acid); and 3,4-dihydroxyphenylacetic acid (DOPAC, orthocatechin).
[0099] The presence of catechol in the composition provides some polyconjugated structure because catechol is oxidized to o-quinone. This causes a visible difference between the unmodified chitosan and the catechol-modified chitosan compositions, which are off-white or pink to dark brown in color, respectively. It should be noted that the catechol-modified chitosan composition changes from pink to brown when oxidation occurs in the catechol.
[0100] By maintaining the pH reaction solution at pH 5.5 or below, a pink coloration in the catechol-modified chitosan is provided in aqueous synthesis, indicating that there is substantially no cross-linking. Pink coloration can also be provided in aqueous synthesis by modifying and subsequently treating steps in the presence of substantially no oxygen, for example, using an aqueous system purged with an inert gas, which inert gas may include, but is not limited to argon or nitrogen. Although it is not desirable to obtain a pink coloration in the final solution or the catechol-modified product, it may be desirable in the intermediate processing stage (for example, dialysis and / or washing of chitosan derivatization and / or subsequent catechol chitosan solution with catechol to remove residual undefined materials), because it can be used for the determination of stable dry polymer storage and dry product weight, and has the product of pure dry catechol-modified substantially redissolved in water to reach the dry weight capacity of expectation subsequently. Then this water-soluble chitosan catechol material is oxidized and cross-linked (brown coloration). However, dried catechol-modified chitosan prior to oxidation is not suitable for use in chitosan dressings formed from the materials of the present invention because dressings including such treated catechol-modified chitosan do not readily re-dissolve and the final solution includes an undesirable mass fraction (>5% w / w) of insoluble particles (>10 microns in diameter). Additionally, catechol chitosan prepared after an intermediate freeze-drying stage is more susceptible to early dissolution in gastrointestinal fluids or the bladder. It should be noted that excessive cross-linking (i.e., brown color) is undesirable in TURP because it can cause dissolution in urine to take longer, e.g., longer than 168 hours when the goal is complete dissolution between about 72 hours and about 168 hours.
[0101] In a preferred embodiment, the catechol-modified chitosan is not removed from the solution by an intermediate drying step for storage, but is kept in an aqueous solution and oxidized in an aqueous solution under conditions of exposure to atmospheric oxygen above about pH 5.5. Preferred pH control is achieved by adjusting the partial pressure of the dissolved carbon dioxide aqueous solution (increased partial pressure reduces pH, while reduced partial pressure increases pH to near pH 7). An alternative preferred mode of pH control is performed by gradually adding a strong acid to reduce pH and by a strong base to increase pH. Examples of strong acids may include, but are not limited to, hydrochloric acid, sulfuric acid, and nitric acid. Examples of strong bases may include, but are not limited to, sodium hydroxide and potassium hydroxide. The subsequent drying of the aqueous water-soluble oxidized catechol-modified chitosan results in a preferred cross-linking level of catechol chitosan, and has good resistance to dissolution and degradation in the upper digestive tract and bladder. The catechol chitosan solution may be diluted with water or concentrated by removing water. Water may be removed by techniques including, but not limited to, ultrafiltration, reverse dialysis, and centrifugation. The solids portion of a solution can be determined by sampling a known volume from the solution and performing analyses including, but not limited to, gravimetric analysis, Fourier transform infrared spectroscopy, UV-visible spectroscopy, refractometry, and specific gravity.
[0102] In a preferred embodiment, the catechol-modified chitosan composition has a brown color due to oxidation of catechol to o-quinone. Quinone is produced by auto-oxidation of catechol hydroxyl groups in the presence of oxygen and at a pH greater than about 5.5. The Schiff base reaction of quinone with the chitosan C-2 amine produces crosslinks in the modified chitosan. The color of the catechol-modified chitosan composition can be controlled by controlling the pH and the amount of oxygen exposure during the synthesis process. Maintaining the pH at or below about pH 5.5 inhibits the production of o-quinone. Subsequently adjusting the dialyzed solution, the final wash or dialyzed catechol chitosan solution to a preferred pH range of 5.8 to 6.2 can provide a more resistant to dissolution, darker, more oxidized catechol. In some embodiments, the coloring of the catechol-modified chitosan dressing characterizes one aspect of the catechol-modified chitosan dressing. In some embodiments, the color reflects the degree of substitution of the chitosan by catechol. In some embodiments, coloration from pink to brown is correlated with the degree of substitution. Fig.15 Exemplary embodiments of different colorations are shown, reflecting and relating to different degrees of substitution of chitosan with catechol.
[0103] To prepare a dry dressing from the catechol chitosan, a preferably light brown to dark brown aqueous catechol chitosan solution is prepared, which can be used alone as itself or can be mixed with other aqueous hydrophilic polymer solutions, including, but not limited to, chitosan and / or optionally a hydrophilic polymer solution. Preferably, the dry phase-separated catechol chitosan dressing is prepared into a dense, dry, frozen phase-separated and fibrous dressing structure.
[0104] Compared to dressings formed substantially from unmodified chitosan, the preferred cross-linked catechol-modified chitosan compositions of the present invention provide good tissue adhesion and 10- to 100-fold increased resistance to dissolution in the upper digestive tract or bladder. For example, Fig.16A , 16B 16C show dissolution test results showing that chitosan dressings disappeared within 15 minutes, while some catechol dressings lasted for more than 24 hours. The catechol-modified chitosan compositions described herein provide heretofore unknown longevity, biocompatibility, and ability to ultimately dissolve.
[0105] Preferred rapid adhesion (≤ 1 minute) to the CGHD or CEHD gastrointestinal mucosa or bladder mucosa formed from the material of the present invention is provided in a dry chitosan dressing by promoting the formation of quaternary ammonium cations on the chitosan glucosamine C-2 in the presence of acid in the dry dressing composition. Preferred acid salts of chitosan in the dressing may include salts of acetic acid, lactic acid, glycolic acid, citric acid, succinic acid, malic acid, hydrochloric acid, glutamic acid, ascorbic acid, malonic acid, glutaric acid, adipic acid, pimelic acid and tartaric acid, and combinations thereof. Preferably, the weight % of the acid salt of chitosan is greater than about 2% and less than about 15%. In order to achieve rapid adhesion to wet tissue (e.g., ≤ 1 minute), the moisture content in the dry gastrointestinal or bladder dressing is preferably less than about 15% by weight; more preferably less than about 10% by weight, and most preferably less than about 5% by weight.
[0106] In the case of a dense frozen phase separation and dry chitosan dressing, a chitosan solution is poured into a frozen phase separation mold (typically in the shape of a pan with a horizontal flat bottom pan), preferably with about 0.1% w / w, more preferably about 0.5% w / w, and most preferably about 0.25% w / w hydrophilic polymer chitosan solution. The hydrophilic polymer solution is preferably added to the horizontal pan to a vertical depth of preferably about 10 mm, more preferably 2.5 mm, and most preferably 5.0 mm mold depth. The solution in the mold is then frozen and dried to a low density (>99% void volume) open or porous dry sponge by sublimation or frozen phase substitution (extraction of ice into the polymer with a non-solvent) having a dry density of < about 0.01 g / cm 3(or, for example, catechol chitosan from a 0.5% solution uncompressed dressing, about 0.005 g / cm 3 ), which is about 0.025 g / cm 3 The dry sponge is then compressed, preferably to a pressure greater than about 0.4 g / cm 3 density and a thickness of less than about 100 microns. Preferred compression is not limited to but may include uniaxial compression between aligned flat plates, wherein the plates are heated to 18°C-150°C and pressure loaded up to 10,000 bar.
[0107] The preferred compression produces a very thin (e.g., about ≤50 microns - about ≤200 microns), strong (e.g., 5 MPa-25 MPaUTS), easily foldable chitosan dressing that can be placed anywhere on the human body in a minimally invasive manner in a limited folded form, which can be deformed without degradation of performance and without compromising the original unfolded dressing form, thereby achieving accurate and effective high surface area placement and attachment.
[0108] Foldability is addressed in the following examples. In one embodiment, the fold test involves folding the final compressed circular dressing in a horizontal plane at the edges into a 180° edge, first folding in a counterclockwise direction, securing the edges together and firmly compressing in the middle of the dressing to form a single linear fold axis (or crease) in the dressing. The folded dressing is then opened and the edge-to-edge fold is repeated on a new fold axis, but in the opposite counterclockwise direction. Success in foldability can be attributed to the absence of visible tears or cracks along the fold axis, and no apparent loss of tensile properties of the dressing (determined by gently pulling through the folds of the dressing). Fig.15 A catechol-modified chitosan dressing is shown that has been folded and unfolded but remains intact with a visible fold axis (crease).
[0109] Freezing phase separation of dilute aqueous polymer solutions results in phase separation of micron- and submicron-thin polymerized chitosan layers regularly interspersed between ice flakes approaching 200 microns in width. Removal of the ice by sublimation (freeze drying) or alternatively by solvent extraction leaves a dry sponge consisting of closely aligned, thin (≤ 1 micron) polymerized chitosan layers. Compression of the polymeric chitosan layer near or above its glass transition temperature (Tg of dry chitosan approaches 80°C) can compress it into a thin (approximately 50 microns) dense polymer structure formed of hundreds of strongly compliant polymerized chitosan leaves (layers) that is not susceptible to interspersed cracks and can be repeatedly folded without failure. Such multi-leaf stratification acquires significant strength. Prior to the present invention, high density frozen phase separated deacetylated chitosan dressings prepared and used as described herein have not been previously studied, which aim to address the key problems addressed by the present invention, such as adhesion, by removing interfering fluids (by absorption, guidance, displacement and / or redirection), the ability to form a folding axis and the ability to resist mechanical failure when repeatedly folded and unfolded along the folding axis.
[0110] In one embodiment, in a non-compressive dressing, the porosity (void space > 99%) is complete and uninterrupted, with pore size ranging from 20-300 microns, with a substantial majority of pores being around 100-200 microns. The continuous pore structure is demonstrated in a compressive dressing by its ability to absorb biological fluids such as blood.
[0111] In some embodiments, after compression, a crack-free clean edge hole approximately 500 microns in diameter can be formed in the dressing by topically applying a narrow gauge (approximately 500 microns in diameter), sharp pointed needle through the dressing and into a flat, hard elastic surface tightly applied to the dressing, which can accept and release the needle point. Preferred receiving support surfaces include, but are not limited to, clean, dry thermoplastic elastomers with a hardness of Shore 55D to 90D. Alternative methods of hole formation can include, but are not limited to, using a small diameter (approximately 500 microns) punch or laser cutting holes.
[0112] In some embodiments, chitosan dressing provided herein has holes on dressing.In some embodiments, hole accommodates fiber or other strengthening attachment elements.This reinforcing element can be formed by simply locally applying reinforcing fluid to be locally combined with the edge of hole.The reinforcing fluid used in the research and development process of the present invention comprises cyanoacrylate glue, which combines the compressed chitosan layer of dressing together, and prevents local delamination and fibrillation of chitosan at hole stress point.Another embodiment of hole reinforcing element is the micro-molding interlocking part (soluble in upper digestive tract or bladder or in the alternative region of the body used) of plastic or metal, and this interlocking part is placed on one side of hole, is permanently assembled with the opposite side of hole, and can support load by hole, and does not cause delamination, fibrillation or other stress-related failures at dressing hole when loading.In some embodiments, micro-molding part can be included in the part on the side connected to delivery device, and this part makes it possible to conveniently carry out insert-type attachment and pull-out type separation of dressing on delivery device.
[0113] As used herein, the term fold axis is intended to refer to a component of a dressing sheet that exhibits memory in bending stress and or folded material and is typically confined to a narrow region of high bending stress and shear forces. A crease in folded paper is an example of a fold axis.
[0114] In a preferred embodiment, the tissue adhesive component of the dressing is formed from a frozen phase separated and dried chitosan sheet having a composition including catechol chitosan. In a preferred embodiment, the non-tissue adhesive component of the dressing is formed from a frozen phase separated dried chitosan sheet without using any modified chitosan. In a preferred embodiment, the non-tissue adhesive component of the dressing is formed from a frozen phase separated dried chitosan sheet without using any modified chitosan. In a preferred embodiment, the non-tissue adhesive component of the dressing is formed from a frozen phase separated dried chitosan sheet without using any modified chitosan. 3 Previously, tissue adhesive and non-tissue adhesive dry sheets had a g / cm 3 density.
[0115] To prepare a dressing from two sheets each having a tissue-adherent surface layer and a non-adherent surface layer, the two sheets are bonded together, for example, by placing one sheet on top of the other on the dressing and applying sufficient uniform pressure thereon to compress them to a higher density. In a preferred method, the original density of each sheet type is ≤ about 0.03 g / cm 3 Increase to a final dressing density of ≥ approximately 0.30 g / cm 3 In a more preferred method, the original density of each sheet is ≤ about 0.015 g / cm 3 Increase to a final dressing density of ≥ approximately 0.4 g / cm 3 In the most preferred method, the original density of each sheet is ≤ about 0.01 g / cm 3Increase to a final dressing density of ≥ approximately 0.5 g / cm 3 At the end of compression, the two compressed sheets are bonded together so that one of the sheets cannot be easily peeled off from the other, and the dressing can be manipulated by folding and rolling without any separation.
[0116] Physical adhesion of materials achieved by compressing two or more low density porous materials together to form a final higher density final two or more layers of porous material solves the problem of how to adhere these materials together without physically or chemically altering the individual materials and without the need for adding other adhesives or bonding agents. It is expected that adhesion can be attributed to micro-surface impact and penetration of the dressing through the pores of the dressing and physical interlocking due to pore compression. This physical interlocking of low density, frozen phase separated dry sheets is not limited to two materials of the same thickness or to only two layers, as the interlocking effect is neither side-dependent nor thickness-dependent. Therefore, it is possible to achieve physical adhesion of materials by compressing two or more low density porous materials together to form a final higher density final two or more layers of porous material. 3 ) are layered and compressed to a density of ≥ 0.3 g / cm3) to form a single frozen phase separated and dried multilayer structure of sheets of the same or different materials of the same or different thicknesses. It is expected that this final physically adhered assembly will provide the advantages of thin top and bottom surface layers, including, but not limited to, adhesive or anti-adhesive materials, providing, including, but not limited to, structural, physical and chemical elements within it.
[0117] In some embodiments, the chitosan dressing has an adhesive side and a non-adhesive side. In some embodiments, the adhesive side of chitosan adheres to the tissue and absorbs and / or redirects surface moisture. In some embodiments, when the chitosan dressing is attached to the injury site, the non-adhesive side is detached from the delivery device, and the chitosan dressing becomes wet. Part of the reason is that the adhesion strength of the chitosan dressing to the tissue surface controls the dressing position when the dressing is detached from the delivery device. As used herein, detachment or "easy detachment" in a double-sided chitosan dressing means that the chitosan dressing (its adhesive surface is applied to the tissue surface or the injury site and adheres due to absorption of moisture) remains on the tissue surface or the injury site, while the non-adhesive side is released from the delivery device, thereby allowing the delivery device to be withdrawn from the injury site without destroying the position of the chitosan dressing on the tissue surface or the injury site. In some embodiments, the chitosan dressing adheres to the delivery device when dry, thereby allowing the chitosan dressing to be delivered to the injury site along with the device.
[0118] In one embodiment, the dressing needs to be locally attached to the delivery device. Typically, these local attachment areas are located at the end of the dressing. For example, a design is to provide local precision connection on the end piece of the dressing on the periphery of the dressing, and there are no other attachment locations to avoid the risk of the dressing being attached to the delivery sheath, delivery device or itself (when rolled / folded). The attachment location can be designed to weaken when wet, or optionally activated to release by a certain type of physical release structure.
[0119] In one mechanism, the chitosan dressing provided by the present disclosure can stop bleeding by absorbing, directing and / or redirecting hydrophilic and hydrophobic fluids at the site of injury. The absorption removes enough moisture from the site of injury to allow a subsequent hemostatic reaction to occur between the chitosan dressing and the tissue at the site of injury, thereby stopping bleeding and keeping the chitosan dressing attached, thereby sealing the site of injury. The porous, dense and multi-layered structure of the chitosan dressing provided herein facilitates the absorption, directing and / or redirecting of moisture at the site of injury, as well as the attachment or adhesion of the chitosan dressing to the site of injury.
[0120] The chitosan dressings disclosed herein are biocompatible. In some embodiments, dissolved residues from a chitosan dressing applied to an injured site in the body safely pass through the digestive tract or urinary tract and are excreted from the body along with other body wastes.
[0121] One or more chitosan dressings can be used or applied to a tissue treatment site or injury site in a continuous manner. When more than one chitosan dressing is deployed, the dressings can be adhered to adjacent tissue sites or injury sites, respectively, or can overlap each other to varying degrees. Due to the thin thickness of the chitosan dressings described herein, it is expected that multiple chitosan dressings can be used as needed to promote or achieve hemostasis of the injury site, depending on the application.
[0122] In one embodiment, the chitosan dressings overlap each other when applied. In this case, it is desirable that the moistened adhesive side of the subsequent dressing has some adhesion to the moistened dressing backing of the earlier dressing. Thus, in one embodiment, the chitosan dressing does not have an anti-adhesive backing, but has a backing with a weak wet adhesion that provides sufficient adhesion for placement of subsequent overlapping chitosan dressings.
[0123] Delivery device
[0124] As used herein, a delivery device is a device for delivering a chitosan dressing. The delivery device delivers the chitosan dressing to different parts of an animal, including humans, pigs, dogs, and the like.
[0125] In some embodiments, the delivery device is a minimally invasive device that can deliver a dressing such as a chitosan dressing to a physiological site in an animal in a non-invasive or minimally invasive manner. In some embodiments, the delivery device is a balloon device. In some embodiments, the delivery device is a wire device or a device laser cut from a small diameter cylinder of nickel-titanium alloy or stainless steel. In some embodiments, the non-invasive or minimally invasive feature of the delivery device is achieved by delivering a dressing such as a chitosan dressing through a narrow catheter or equivalent working channel. In some embodiments of CGHD, the diameter of the catheter or equivalent working channel is less than 3.2mm. In other CGHD embodiments, the diameter of the gastroscope channel can be 2.8mm-4.5mm. In some CEHD embodiments, the diameter of the balloon catheter or equivalent working channel is less than about 7mm. In other CEHD embodiments, the diameter size of the channel of the TURP delivery device can range from 5mm-7mm.
[0126] In some CGHD embodiments, the catheter or balloon catheter or equivalent working channel has a diameter of less than 3.2 mm. In other CGHD embodiments, the diameter of the gastroscope channel can be between 2.8 mm and 4.5 mm.
[0127] In some CEHD embodiments, the catheter or balloon catheter or equivalent working channel has a diameter of less than about 7 mm. In other embodiments, the diameter of the channel of the TURP delivery device may range in size from 5 mm to 7 mm.
[0128] Exemplary delivery devices include, but are not limited to, balloon devices, balloon catheters, wire devices, cylindrical devices with laser cut ends, indwelling catheters, urethral or suprapubic catheters, external catheters, short-term catheters, and intermittent catheters.
[0129] The delivery device may also be an endoscopic device used in various aspects of medical procedures.In some embodiments, the endoscopic device is non-invasive or minimally invasive due to the narrow catheter or tube / pipe or similar narrow diameter portion of the device.
[0130] The delivery device may also be a transluminal or transurethral delivery device. In some embodiments, the transurethral delivery device is non-invasive or minimally invasive due to the narrow catheter or tube / pipe or similar diameter portion of the device.
[0131] The delivery device includes a tube or catheter having a narrow diameter or other device of similar structure.
[0132] Attachment of dressing to delivery device
[0133] CGHD
[0134] The frozen phase separated dressing consists of compacted brittle layers and layers prone to delamination that require special attachment of the dressing to the wire and cylindrical laser cut delivery device. Each attachment point of the dressing to the delivery device must be able to withstand a load of 50-100 g during rolling and unrolling of the dressing. Directly adhering the dressing to the delivery device (e.g., by cyanoacrylate glue) is not an option for frozen phase separated dressings formed from fully dissolved solutions due to the low cohesive strength of the surface layer. A less problematic embodiment is one in which the catechol chitosan is formed from carbonated chitosan dissolved in carbonic acid, wherein the alkaline precipitation and subsequent washing of the pure chitosan hydrogel with water before dissolving in carbonated chitosan comprises a dispersion of solid chitosan fibers (≥0.2% w / w chitosan) that are insoluble in carbonic acid, which can provide reinforcement for the subsequent catechol modified chitosan from the carbonate solution. In addition to this example of chitosan fiber reinforcement of the frozen phase separated bulk and surface structure of low carbonated chitosan (0.2%-5% w / w chitosan) dressings, the preferred means of local reinforcement and attachment of the dressing to the delivery device in the case of wire delivery is by placing small diameter (approximately 500 microns) holes with reinforcement elements throughout the dressing at the point of attachment to the delivery device.
[0135] Preformed holes in frozen phase separated dry dressing sponges are the preferred way to form receiving holes in uncompressed dressing sponges. Since low density uncompressed sponges (<0.05 g / cm3) are prone to delamination, are very fragile, and are therefore not amenable to conventional punching methods involving any load on the sponge, the preferred method for punching holes in these sponges without damaging the sponge layer structure is to apply an insulating hydrophobic (non-sticky) rod-shaped mandrel to the molding solution (starting from the top of the solution, through the solution to the other side and contacting the bottom surface of the mold, preferably through the bottom surface and into the bottom of the mold), and then immediately perform frozen phase separation of the solution. These mandrels can be conical so that they can be easily removed after the frozen phase separated sponge is dried. It is expected that such mandrels will be made of rigid or semi-rigid hydrophobic materials that can be machined or molded. Suitable mandrel materials include, but are not limited to, fluorinated materials Teflon TM and Kel-F TMAnd high density polyethylene (HDPE). The diameter of the hole formed after removing the mandrel is designed to be convenient to pass through the fragile uncompressed sponge without damaging the sponge. The mandrel can be supported in the mold by slotting into a receiving hole of suitable size on the mold substrate surface. Or, they can be supported by a releasable hydrophobic film, which is immediately placed on the upper surface of the frozen phase separation mold and the mold solution. In the case of dry frozen phase separation solution, the film is removed from the frozen phase separation surface before drying, and the mandrel is left in place. After drying, the preformed hole is therefore ready to accommodate the tie-down line, so that the dressing is attached to the delivery / deployment device. The tie-down line is placed in the sponge before being compressed by a suitable arrangement, to withstand all the forces of the dressing rolling up, unfolding and delivering. The sponge compression (from low density <0.05g / cm3) is compressed to high density (>0.4g / cm3) and the tie-down line and any other strengthening / fixing element are locked in place. The threads may be glued in place before or after the pressurized compression of the material, or a liquid reinforcing element such as cyanoacrylate glue may be locally applied through the holes using the threads and the threads removed after application. An alternative embodiment for forming suitable holes in the uncompressed sponge for receiving support threads or other types of support elements is by laser hole cutting.
[0136] After compression, a clean, crack-free edge hole approximately 500 microns in diameter can be formed in the dressing by topically applying narrow gauze (approximately 500 microns in diameter) and passing a sharp, pointed needle through the dressing and into a flat, hard, elastic surface tightly applied against the dressing that can accept and release the needle tip. Preferred receiving support surfaces include, but are not limited to, using a clean, dry thermoplastic elastomer with a hardness of Shore 55D-90D. Alternative methods of hole formation can include, but are not limited to, using a small diameter (approximately 500 microns) punch or laser cutting holes.
[0137] The hole in the dressing can accommodate fiber or other reinforcement attachments. This reinforcement element can be formed by simply locally applying a reinforcing fluid to be locally combined with the edge of the hole. The reinforcing fluid used in the research and development of the present invention comprises cyanoacrylate glue, which combines the compressed chitosan layers of the dressing together, and prevents local delamination and fibrillation of the chitosan at the hole stress point. Another embodiment of the hole reinforcement element is a micro-molded interlocking component (dissolvable in the upper digestive tract or the alternative region of the application body) of plastic or metal, which is placed on a side of the hole and the relative hole side to be permanently fixed together and can support the load through the hole, and when loaded, delamination, fibrillation or other stress-related failures at the dressing hole can not be caused. It can be expected that such a micro-molded component can be included in the part on the side attached to the delivery device, which makes it possible to easily separate the dressing quick snap-on attachment and demoulding (snap-off) to the delivery device.
[0138] General delivery device release of the dressing can be achieved by a variety of methods, including demoulding. A preferred method of dressing release is by using a delivery device to attach fibers to the dressing that are strong when dry but weak when wet. Such fibers include, but are not limited to, chitosan fibers that have been treated to be rapidly water soluble. Preferred chitosan fibers are water soluble multifilament fibers that have a strength of >30 MPa when dry and <0.1 MPa when wet.
[0139] CEHD (Connection of TURP Dressing to Balloon)
[0140] In one embodiment, the circular dressing is folded once from edge to edge on itself, and then the folded dressing (now half) is folded again from edge to edge on itself (now one quarter). The dressing is unfolded, and there are now two fold lines passing through the middle of the dressing. The trajectory of the circumference of the catheter is drawn in the middle of the dressing (a small central circle). Use scissors points or other sharp cutting tools to cut along the intersecting fold lines in the middle of the dressing to the drawn circumference of the catheter. Once the fold lines are cut, four triangular windows or catheter connecting pieces will appear in the middle of the dressing. The catheter can pass through the central opening in the dressing, and the dressing piece can be connected by double-sided tape or other application and sticking methods to fix the small piece on the desired position of the catheter, thereby fixing the main body of the dressing on it close to the catheter balloon. Preferably, the dressing piece is preferably placed on one side of the dressing, which is back to back with the catheter balloon, and the dressing piece is folded on it. Preferably, the adhesive used to attach the tab to the catheter is water soluble to allow the dressing to slide out of the catheter and remain in place after pressure is applied via the balloon catheter (with optional catheter removal).
[0141] Therapeutic applications and methods
[0142] Embodiments of chitosan dressings formed by materials of the invention provided in the present disclosure can be used to stop bleeding in specific diseases, disorders, disorders or emergency trauma or injuries. In some embodiments, dry solid chitosan materials of the present invention can be used to stop bleeding from any wet physiological surface such as mucus. Exemplary applications include, but are not limited to gastrointestinal or bladder bleeding, other intracavitary applications, including vascular applications, internal surgical bleeding, internal biopsy bleeding, internal bleeding after solid organ resection, and oral, ocular, auditory or nasal bleeding. It is also contemplated that water or fluid may need to be added to promote other applications of chitosan dressings adhering to tissue surfaces or sites of injury, for example, chitosan dressings are applied on external surfaces.
[0143] The dry chitosan material of the present invention can be used to treat gastrointestinal bleeding, including, but not limited to, treatment of esophageal varicose bleeding, peptic ulcer bleeding, duodenal ulcer bleeding, upper and lower digestive tract biopsy-related bleeding resection, upper and lower digestive tract resection, and upper and lower digestive tract tear or rupture. Other diseases, conditions, disorders or acute trauma or injuries can include, but are not limited to internal arterial injury; internal bleeding in the liver, internal bleeding in the vena cava; chest cavity injury, including perforation of the heart and lungs and their blood vessels; and abdominal cavity injury.
[0144] The chitosan materials of the present invention may also be used to treat transurethral prostatectomy and bladder neck bleeding, including but not limited to the treatment of hemorrhage.
[0145] The chitosan material of the present invention can also be used after acute internal injury (such as occurs during UGIB, TURP or other minimally invasive or open surgery) to protect the injured area by sealing the injured area and providing an environment conducive to cell regeneration, and then dissolve or degrade within 7 days.
[0146] For general therapeutic purposes, the chitosan materials of the present invention can also be used for delivery to or local attachment to specific target sites, including delivery of active pharmaceutical agents and / or biologics. Such target sites include, but are not limited to: anastomosis, esophageal varices, peptic ulcers, excised prostatic fossa, liver resection and biopsy, kidney resection and biopsy, bladder resection and biopsy, laryngeal resection and biopsy, pancreas resection and biopsy, stomach resection and biopsy, lower gastrointestinal tract resection and biopsy, lung resection and biopsy, and heart resection and biopsy.
[0147] The above different embodiments can be combined to provide additional embodiments. All U.S. patents, U.S. patent application publications, U.S. patent applications, foreign patents, foreign patent applications and non-patent publications related to and / or listed in the application data sheet in this specification, including, but not limited to, the entire contents of U.S. Provisional Patent Application Nos. 62 / 612,013 and 62 / 631,290 are fully incorporated herein by reference. If it is necessary to adopt the concepts of different patents, applications and publications to provide further embodiments, then various aspects of the embodiments can be modified.
[0148] These and other changes can be made to the embodiments in light of the above detailed description. Generally, in the following claims, the terms used should not be interpreted as limiting the claims to the specific embodiments disclosed in the specification and claims, but should be interpreted to include all possible embodiments and the full range of equivalents to which these claims are entitled. Therefore, the claims are not limited by this disclosure. Example
[0149] Examples 1-6 relate to CEHD chitosan dressings.
[0150] The following materials and articles are contemplated in the present method of chitosan intracavitary hemostatic dressings.
[0151] Chitosan A: Primex ChitoClear 65010, TM 4375, MW = 250-300 kDa, Brookfield
[0152] Chitosan B: Primex ChitoClear 43000, TM 4167, MW = 110-150 kDa, Brookfield viscosity of 1.0% w / w chitosan solution in 1.0% acetic acid at 25°C and spindle LV1 = 9 cPs, DDA = 95% (by colloid titration).
[0153] Glacial acetic acid: Fisher Scientific, catalog number A38-212.
[0154] Hydrochloric acid: 1.0 M aqueous solution Sigma Aldrich, catalog number H9892.
[0155] L-Lactic Acid: JT Baker, Cat. No. 0196-01.
[0156] Glycolic Acid: JT Baker, Cat. No. M821-05.
[0157] Sodium hydroxide: 5.0 M NaOH aqueous solution Sigma Aldrich, catalog number S8263-150 ml.
[0158] Potassium hydroxide: 0.1 M KOH in methanol (BDH).
[0159] Ethanol: 200° Proof Sigma Aldrich, catalog number 459844-1L.
[0160] Acetic anhydride: ACS reagent grade, obtained from Sigman Aldrich, catalog number 320102-1L.
[0161] 3,4-Dihydroxyhydrocinnamic acid (hydrogenated caffeic acid): 98% Sigma Aldrich, catalog number 102601.
[0162] 3,4-Dihydroxycinnamic acid (caffeic acid): 98% Sigma Aldrich Cat. No. C0625
[0163] Trans-3,4-dihydroxycinnamic acid (trans-caffeic acid): Sigma Aldrich catalog number 51868
[0164] 3,4-Dihydroxyphenylacetic acid (DOPAC, epigallocatechin-3-yl) catechin: 98% Sigma Aldrich Cat. No. 850217.
[0165] 1-Ethyl-3-(-3-dimethylamino-propyl)-carbodiimide: (or N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, with the common acronym EDC) Sigma Aldrich, catalog number E7750.
[0166] N-Acetyl-L-cysteine Sigma Aldrich, catalog number A7250
[0167] Sodium chloride Sigma Aldrich, catalog number 793566-500g.
[0168] Glycerol: Sigma Aldrich, catalog number G-8773.
[0169] Polyethylene glycol: Spectrum, catalog number PO108.
[0170] Polyethylene oxide: Mw 400,000 da, Sigma Aldrich Cat. No. 372773-500G.
[0171] Poloxamer 407: Spectrum, catalog number P1166.
[0172] Sucrose: Sigma Cat. No. S3929.
[0173] D-Sorbitol:Sigma Catalogue S1876
[0174] Hydroxypropyl cellulose (HPC): Aldrich catalog number 191892
[0175] Hydroxyethyl cellulose (HEC): Aldrich catalog number 308633.
[0176] Synthetic urine preparation: Add calcium chloride dihydrate Sigma catalog number C5080 (1.30 g); magnesium chloride hexahydrate Sigma catalog number M2670 (1.30 g); sodium chloride Sigma catalog number 793566 (9.20 g); sodium sulfate Aldrich catalog number 238597 (4.60 g); sodium citrate dihydrate Sigma catalog number S4641 (1.30 g); sodium oxalate Sigma catalog number 718 00 (0.04g); potassium dihydrogen orthophosphate Sigma catalog number P5655 (5.60g); potassium chloride Fisher catalog number BP366 (3.20g); ammonium chloride Sigma catalog number 09718 (2.00g); urea Sigma catalog number U1250 (50.00g); creatinine Acros catalog number 228940500 (2.20g) to a 2.0 liter volumetric flask, add 1.5 liters of deionized water to dissolve. After the ingredients are dissolved in water and the solution temperature is equilibrated to room temperature, use deionized water to reach the 2.0L mark.
[0177] Porcine bladder with urethra, Animal Biotech Industries Inc., (Danboro, PA 18916)
[0178] Pork Intestine Casings, Butcher and Packer (29 / 32mm) (Madison Heights, MI 48071)
[0179] Citrated bovine whole blood: Lampire Biological Laboratory Bovine CPD, catalog number 7720010.
[0180] Cyanoacrylate A: Permabond 910 tissue adhesive, catalog number 72590.
[0181] Cyanoacrylate B: Loctite 4902 Instant Adhesive Catalog No. 1875841
[0182] Dialysis tubing: 3,500Da MWCO Snakeskin dialysis tubing (Fisher Scientific), catalog number PI88244.
[0183] Sealing film: "M" laboratory film, Pechiney Plastic Packaging (Chicago, IL 60631)
[0184] Adhesive: Double-sided 3M catalog number 21200-46144-6 (St Paul, MN 55144)
[0185] Scotch Fine Line Tape 218, 3M Catalog No. 70-0060-4397-3 (St Paul, MN 55144)
[0186] Example 1
[0187] Preparation and Characterization of Catechol Chitosan
[0188] The synthesis of catechol chitosan is an N-acylation reaction between a catechol molecule containing a terminal carboxylic acid and the C-2 amine of the glucosamine polymer of chitosan (see Figure 7 ). The reaction is carried out in dilute aqueous solution at room temperature under controlled pH. Fig. 12A and 12B A number of examples of modified formulations of catechols for use in the articles of manufacture of the present invention are provided. Fig. 12B A list of dressing products is provided in column 1 of the . The formulations of the products are listed in Fig. 12B Column 2. Catechol chitosan preparations have the acronym "Cs-Cat". The Cs-Cat preparation number is provided immediately after "Cs-Cat" and is written as "Cs-Cat,XX, where XX is a number representing the catechol chitosan preparation number. Chitosan solutions are prepared and they are typically written as "Chitosan" or "Cs" with an acid (lactic or acetic acid) to provide an aqueous solution. HPMC is hydroxypropyl methylcellulose. HPC is hydroxypropyl cellulose, and HEC is hydroxyethyl cellulose. The batch number of chitosan is shown in column 3. Chitosan ( Fig. 12B The catechol substitution degree of the 4th column of the quartz UV test cell, path length 1 cm, x2 (HACH Co., catalog number 48228-00) was determined as follows: A quartz UV test cell, path length 1 cm, x2 (HACH Co., catalog number 48228-00) was used to obtain the UV / vis spectrum. The UV / Vis spectrophotometer was a Varian Cary Bio 100. A standard solution of 3,4-dihydroxyhydrocinnamic acid was prepared with water and the absorbance at 280 nm was plotted against the concentration. The extinction coefficient ε in the Beer Lambert relation, shown below, was used for the absorbance in the dilute solution.
[0189] A=ε·c·l
[0190] A is the absorbance (dimensionless), and l is the path length.
[0191] (absorbance < 0.5) was determined to be 2,540 ± 50 liters / (mol.cm). This value was used to determine the degree of substitution in the modified chitosan in a known mass of a dilute aqueous solution of the modified chitosan, a known volume of solution and the peak absorbance measured at 280 nm.
[0192] Dilute the chitosan catechol solution so that its absorbance at 280 nm is less than 0.5 (usually about 1:50 or 1:100). Use the absorbance, the weight of the solution used in the dilution, and the percent solids (CS-catechol) to determine the fractional substitution (f) of HCA relative to the free amines on the chitosan backbone according to the following equation: DS ):
[0193]
[0194] Where A is the UV / vis absorbance of the modified chitosan at 280 nm; V is the volume (liters) of the modified chitosan solution obtained after drying to a constant dry mass; m CC is the measured dry mass of catechol-modified chitosan (g); f DDA is the fraction of the degree of deacetylation of chitosan.
[0195] The percentage of solute (mainly hydrophilic polymer) in the solution is as follows Fig. 12B as shown in column 5 of . Fig. 12B Column 6 of provides the depth of solution poured into the flat well mold for frozen phase separation. During freezing, the pour depth remained essentially constant so that when compared to the last set of compressed dressings ( Fig. 12B The depth of pouring provides a useful indication of the degree of compression change. The final density of the dry compression dressing is Fig. 12B is provided in column 8 of the Fig. 12B Column 9 of the TABLE 1 provides any additional information about the dressing product. It is interesting to note that Dressing 17 was processed to a high degree of dryness, while Dressing products 71, 79, 80, 83, 84 and 85 were all processed by co-compression with non-catechol chitosan dressings. These non-catechol chitosan dressings used as backing were all formed from 5 mm pours of 430,000 0.5% w / w chitosan acetic acid solution.
[0196] Examples of catechol chitosan synthesis are shown in the six method variations provided below.
[0197] Method 1
[0198] CS-catechol, batch number 15:
[0199] Chitosan (1.51 g) was dissolved in deionized water (140 g) and 1.0 M HCl (5 mL). A 1:1 v / v solution (145 mL) of deionized water and ethanol was prepared. 3,4-dihydroxyhydrocinnamic acid (HCA; 10.5 mmol) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC; 13.0 mmol) were dissolved in a water / alcohol solution. Next, the water / alcohol solution was slowly added to the chitosan solution prepared above, and the reaction mixture was stirred and placed. The pH of the reaction mixture was maintained at 5.5 using a 5.0 M NaOH solution and reacted overnight. After the overnight reaction, the solution was dialyzed against 5 L deionized water acidified with 1 drop of 1.0 M HCl solution for 3 days and against deionized water for 4 hours. The dialysate was changed regularly throughout the dialysis period (at least every 24-48 hours).
[0200] Method 2
[0201] CS-catechol, batch number 22-1:
[0202] Chitosan (9.03 g) was dissolved in deionized water (126 g) and 1.0 M HCl (30 mL). The pH of the solution was then brought to 5.1 using 1.0 M NaOH solution. A 1:1 v / v solution of deionized water and ethanol (150 mL) was prepared and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC; 31.3 mmol) was dissolved in the water / alcohol solution. 3,4-Dihydroxyhydrocinnamic acid (HCA; 15.7 mmol) was dissolved in deionized water (15 mL). Next, the HCA solution was slowly added to the chitosan solution prepared above and the reaction mixture was placed under overhead stirring. The EDC solution was then slowly added to the HCA / chitosan solution. The pH of the reaction mixture was maintained at 4.9 using 0.1 N KOH methanol solution. After reacting overnight, the solution was dialyzed for 4 days against 5 L of deionized water acidified with 1 drop of 1.0 M HCl solution. The dialysate was changed regularly throughout the dialysis period (at least every 24-48 hours).
[0203] Some of the solution separated from CS-catechol batch 22 after dialysis was placed in an oven to concentrate the solution. The solution was baked at 80°C and the volume was reduced by about one third.
[0204] Method 3
[0205] CS-catechol, batch 32 (prototype A, acute in vivo I):
[0206] Chitosan (1.504 g) was dissolved in deionized water (143.5 g) and 1.0 M HCl solution (5.0 mL). The pH of the solution was then brought to 5.5 with 1.0 M NaOH solution. A 1:1 v / v solution (150 mL) of deionized water and ethanol was prepared by dissolving N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC; 2.93 mmol) and 3,4-dihydroxyhydrocinnamic acid (HCA; 10.41 mmol) in a water / alcohol solution. Next, the water / alcohol reactant solution was slowly added to the chitosan chloride solution. The pH was controlled at 4.9-5.5 using a 1.0 M NaOH solution during the addition of the reactants to the chitosan solution. After the addition of the reactants, the reaction mixture was monitored for 2-4 hours, and the pH was controlled at 5.4-5.7 using a few drops of 1.0 M HCl and 1.0 M NaOH as needed. Next, the pH was controlled at 5.5 and the reaction was maintained overnight. After the reaction was overnight (approximately 18-24 hours), the pH of the chitosan catechol solution was controlled back to 5.5. Next, the chitosan catechol was dialyzed against 5L of deionized water at about pH 5.8 for 5 days and against deionized water at about pH 6.1 for 4-24 hours. The dialysate was changed regularly throughout the dialysis operation (at least every 24-48 hours).
[0207] Method 4
[0208] CS-catechol, batch number 33
[0209] Chitosan (0.507 g) was dissolved in deionized water (47.5 g) and 1.0 M HCl solution (2.0 mL). The pH of the solution was then brought to 5.5 with 5.0 M NaOH solution. A 1:1 v / v solution of deionized water and ethanol (50 mL) was prepared, and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC; 2.94 mmol) and 3,4-dihydroxyhydrocinnamic acid (HCA; 1.49 mmol) were dissolved in a water / alcohol solution (-Reactant Solution-). Next, the water / alcohol reactant solution was slowly added to the chitosan chloride solution. The pH was controlled at 5.4-5.6 for 2.5 hours. The pH was then controlled to 5.4 and the reaction was kept overnight (about 18-24 hours). The pH of the resulting chitosan catechol solution was controlled at about 5.5 and then dialyzed for 3 days at about pH 5.8 and 3 days against deionized water. The dialysate was changed regularly throughout the dialysis operation. After dialysis, the solution was allowed to evaporate excess water obtained during the dialysis process by hanging it in a dialysis tubing in a fume hood overnight. The solution was left to stand until it regained its pre-dialysis weight.
[0210] Method 5
[0211] CS-catechol, batch number 35
[0212] Chitosan (1.681 g + 10.6% w / w humidity) was dissolved in deionized water (143.5 g) and 1.0 M HCl solution (11 mL). The pH of the chitosan chloride solution was then brought to about 5.5 with 1.0 M NaOH solution. A 1:1 v / v solution of deionized water and ethanol was prepared (150 mL), and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC; 8.76 mmol), 3,4-dihydroxyhydrocinnamic acid (HCA; 2.39 mmol) and N-acetyl-L-cysteine (NAC; 2.36 mmol) were dissolved in a water / alcohol solution (-Reactant Solution-). Next, the reactant solution was added to the chitosan chloride solution. The pH of the reaction mixture was controlled at 5.2-5.3 during the addition of the reactant solution. After 2 hours, the pH of the reaction mixture was brought to about 5.4. The solution is then kept to react overnight (about 18-24 hours). After reacting overnight, the pH of the solution is controlled to about 5.5. The solution is dialyzed against 5L of deionized water for 6 days. The dialysate is changed regularly throughout the dialysis operation (at least every 24-48 hours).
[0213] Method 6
[0214] CS-catechol, batch number 38
[0215] Chitosan (1.678 g + 10.6% w / w moisture) was dissolved in deionized water (143.3 g) and 1.0 M HCl solution (8 g). The pH of the chitosan chloride solution was then brought to about 5.5 using 1.0 M NaOH solution. A 1:1 v / v solution (150 mL) of deionized water and ethanol was prepared, and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (EDC; 2.95 mmol), 3,4-dihydroxyhydrocinnamic acid (HCA; 1.475 mmol) were dissolved in the water / alcohol solution (-reactant solution-). Next, the reactant solution was added to the chitosan chloride solution. The pH of the reaction mixture was controlled to be close to pH 5.5 during the addition of the reactant solution. After 2 hours, the pH of the reaction mixture was adjusted to 5.51. The solution was then kept reacting in a covered beaker at room temperature for 20 hours. After 20 hours, the pH of the solution was 5.54. The solution was divided into 3 batches close to 100 g of solution in dialysis tubing and dialyzed against 5 L of deionized water for 5 days, with a pH of 5.8-5.9 in the first 3 days and a pH of 6.2 on the 4th day. The dialysate was changed regularly throughout the dialysis operation (every 24 hours).
[0216] Example 2.
[0217] Hydrophilic polymer dressing with frozen phase separation
[0218] In a 500 ml, 1000 ml or 2000 ml Nalgene LDPE bottle or polypropylene beaker, prepare an aqueous hydrophilic polymer solution by adding ingredients including, but not limited to, the previously prepared solution, hydrophilic polymer, water, acid, and other ingredients. Fig. 12B The 85 formulation types studied are listed.
[0219] The major issues encountered when formulating for transurethral prostatectomy administration of dressings that come in direct contact with urine are: 1) rapid (usually <30 min) urine-promoted dissolution of chitosan; 2) interference from blood in achieving rapid adhesion to pure catechol-modified chitosan; 3) susceptibility to dressing rupture and tearing when changes are made to the product to address dissolution and adhesion issues. The % w / w of the final hydrophilic polymer solution is 0.1%-4% polymer by weight. The capped bottle and its contents are continuously mixed at room temperature for 12-24 hours using an IKA KS260 orbital shaker or a Wheaton benchtop bottle roller to achieve complete solution homogeneity. The beaker solution is mixed on a magnetic stir plate with magnetic stir beads at room temperature for 12-24 hours to achieve solution homogeneity. During mixing, the beaker is isolated from the external environment using a parafilm. When suspension conditions are not present, the solution prepared for frozen phase separation is essentially homogeneous and clear. The catechol chitosan solution showed some turbidity and milky appearance, indicating the presence of some dispersed fine catechol chitosan spherical particles.
[0220] A chitosan solution is prepared as a frozen phase-separated dressing, wherein the weight % hydrophilic polymer of the final solution is 0.25%-4% w / w aqueous solution. The frozen phase separation is carried out in a Teflon-coated aluminum mold hole with a horizontal flat bottom. The solution is poured into the hole to a height of preferably no more than about 10 mm, more preferably 2.5 mm, and most preferably 5.0 mm from the bottom of the mold. Cooling is applied through the bottom of the mold to the solution in the mold, which is initially at a temperature of 15°C-30°C before freezing, and then frozen. Although other cooling temperatures can be applied to achieve a suitable frozen phase-separated structure, it is preferred that the cooling temperature applied to the shelf is -40°C, more preferably -55°C, and most preferably -45°C. After the solution reaches frozen phase separation and the temperature of the frozen solution reaches equilibrium at the freezing temperature, the system is further frozen phase separated and re-equilibrated for at least 1 hour before drying. In an improved freezing and mold filling method to accommodate different frozen phase separation solution layers, the first layer is added to the mold to a preferred depth and frozen, then the second layer is added and frozen, and then a multi-layer frozen phase separation dressing is prepared in this way. Care should be taken to ensure that there is no frost between the (n-1)th frozen solution and the nth poured solution, and the difference in the frozen structure between the layers may cause cracking. The delamination of the separate frozen layers that adhere to each other is a significant problem. During this research process, the discovery of a successful method for delaminating and adhering a single layer of pre-dried hydrophilic polymer matrix to a single co-adhered compressed multi-layer composite sheet is an unexpected and important discovery.
[0221] The isolated frozen solution patches were subjected to sublimation freeze drying using a 24 square foot shelf Virtis Benchmark 2000 pilot scale freeze dryer. In the primary freeze drying (removal of ice not hydrogen bonded to the hydrophilic polymer), the frozen patches equilibrated in their molds were depressurized to ≤300 mTorr in the freeze dryer, and the freeze dryer condenser was set to ≤-65°C, and the freeze dryer shelf was heated to promote sublimation of ice from the frozen isolated patches without raising the patch temperature above -15°C. After substantially all unbound ice was removed, the shelf temperature was raised to approximately 25°C to remove hydrogen-bound ice and reduce the moisture in the dried dressing matrix to a residual water content of no more than 4% in the dry dressing. The final dried matrix conformed to the original shape of the filled mold, with a shrinkage of nearly 5% in length and width, and a density of 0.005 g / cm3-0.04 g / cm3. They contain more than 95% void space and they are interporous structures with fine polymer layers (submicron to 5 micron thickness) and voids between adjacent layers of 100 to 300 microns.
[0222] After freezing phase separation and drying, the dried matrix is compressed from its original thickness (10mm-2.5mm) to a final thickness preferably close to 50 microns. If two uncompressed dressings are compressed in a manner one above the other, they will be permanently bonded together at the end of the compression process. A calibrated shim of uniform thickness can be used in compression to achieve a desired compression dressing thickness that is substantially identical to the shim thickness. There are a variety of methods to achieve this compression, with a desired compression setting close to 50 microns. The preferred compression method used in this study is to compress the entire dry uncompressed dressing (size typically close to 100mm long x 100mm wide x 2.5mm high or 50mm diameter x 2.5mm high) to a thickness between the aligned press plates of ≤100 microns, with a uniaxial compression rate of ≤0.5mm / min. The press plates (Mic 6 Aluminum 300mm x 300mm x 90mm with diamond coating or Teflon coating) were machined to a flat surface (≤ 5 microns in 300mm) with no or some controlled texture on the machined surface. During compression, the temperature of the press plate was preferably maintained near 80°C for 3-5 minutes of uniaxial compression. Compression was achieved by loading screws at the four corners of the press plate with a load of up to 4 tons at each corner. Compression was continued for at least 2 minutes before releasing the load. The compressed thickness and weight of the novel compressed hydrophilic polymer matrix were measured. The final density was 0.25-0.9 g / cm 3 After compression, the dressing is further processed. This additional processing includes die cutting into 2.5 cm diameter test pieces and in some cases a thermal annealing heat treatment (heating in a convection oven at 60°C-150°C for 5-30 minutes). At the end of processing, the dressing is placed in an aluminum foil bag with a zip lock or heat seal. Packaged dressings intended for animal and biocompatibility testing are irradiated with 25 kGy gamma rays.
[0223] Example 3.
[0224] In vitro and ex vivo testing of chitosan
[0225] Prototype of intracavitary hemostatic dressing
[0226] In vitro beaker test
[0227] The dissolution behavior of CEHD was studied under conditions similar to those experienced during TURP in vivo use. Dissolution was monitored for up to 7 days to ensure that CEHD dissolution met the target resistance for early dissolution (within the first 24 hours) and subsequent subsequent dissolution such that no residual CEHD remained after 168 hours (7 days).
[0228] The pig bladder tissue slices (25mm x 25mm x 3mm) with the mucosal surface facing outward were fixed to the bottom of a 200-ml polystyrene beaker with cyanoacrylate glue. A solution of 1:250v / v blood in standard saline was dripped onto the upper surface of the ex vivo sliced bladder tissue. By applying a 500-gram standard weight (Troemner, Thorofare NJ08086) to a probe of 2.54cm diameter for 5 minutes, a CEHD dressing sheet (1.3cm x 1.9cm) was applied to the moistened tissue surface with a pressure of 9.7kPa (73mmHg). Sufficient synthetic urine (50ml) was added to the beaker at room temperature to immerse the CEHD sheet. The beaker was covered with a sealing film, incubated at 37°C (Fisher Scientific Model146E, CAT.97-990E), and placed on a shaker (IKA AS260.1, KS260) at 120rpm. The synthetic urine was changed every 24 hours and dissolution behavior was recorded at regular intervals depending on the amount of dressing present until complete dissolution or up to 168 hours. In certain tests, the adhesion of the CEHD test piece to tissue was assessed by a horizontal scraping motion of forceps to measure resistance to shear forces. The CEHD tissue adhesion test was performed on a pass or fail basis in the in vitro dissolution test and was noted as low, medium, or high.
[0229] The results of in vitro dissolution and adhesion to porcine bladder mucosa are as follows Fig.15 The in vitro dissolution and adhesion to porcine bladder mucosa results were used together with the results of the folding and device deployment tests to select three preferred dressing types for biocompatibility and in vivo testing. These dressing types include catechol-modified chitosan preparations and catechol and thiol chitosan modified preparations. The preferred ex vivo dressing types are labeled A, B, and C. Dressing batches 71 and 81 represent type A dressings; batches 78 and 83 represent type B dressings, and batches 75, 80, and 84 represent type C dressings.
[0230] In vitro simulated venous wound closure (SVWS) test
[0231] A laboratory simulated vein wound seal (SVWS) device was constructed to test the sealing ability of CEHD adhered to a 1.5 mm diameter "injury" hole in the center of a standard PVC plate, which has previously been shown to mimic the dermis in terms of mucoadhesive chitosan binding to the dermis, for 5 minutes by 1 drop of diluted blood, 1:250 v / v blood in standard saline, and a 9.7 kPa load. Silastic Laboratory Tubing, size - 0.250 ID x 0.375 OD, Dow Corning Corporation (Midland, MI 48686) An open reservoir of citrated bovine whole blood was connected to the orifice through a stop valve immediately before the orifice. The vertical height relative to the level of blood in the reservoir above the orifice was adjustable from 0.0 to 50 cm. After the CEHD test dressing was fixed in the center of the hole of the standard PVC surface, the stop valve was opened and the dressing was observed for 15 minutes and evaluated (pass / fail) for its ability to maintain a seal (no blood leaking through or under it). The pressure head was recorded in each test. This test provides a rapid simulated hemostasis test of the CEHD prototype under venous bleeding pressure.
[0232] The simulated bleeding rate (g / min) was determined by the difference in weight between a pre-weighed absorbent sheet and the same absorbent sheet placed at the "injury" site, sampling flowing blood for 15 seconds and multiplying by four.
[0233] At 23° C., a top height difference of 20 cm-42 cm corresponds to a pressure of 14.7 mmHg-30.9 mmHg (typical values of venous pressure in prostatic bleeding). The bleeding rates at the 20 cm and 42 cm height differences were determined to be 4.7 g / min and 8.0 g / min, respectively.
[0234] The in vitro simulated venous wound closure (SVWS) test results for 25 kGy gamma irradiated dressings batches B and C are provided in Table 1 (0 and 6 months shelf life for foil packaging stored at 25°C).
[0235] Table 1.
[0236] In vitro simulated venous wound closure (SVWS) test results.
[0237]
[0238] Ex Vivo Flow Testing of a 10mm x 10mm Dressing Attached to a 3mm Diameter Perforation in a SIS
[0239] Test dressings that will perform well in vitro (Dressings Type B and C, N=10 each) - see Fig. 12A , 12Band 15) were adhered for approximately 3 minutes at a balloon pressure of approximately 7 psi to focus the porcine small intestinal submucosa (SIS) onto a 3 mm diameter hole in the SIS, which was supported by a custom glass test cell from Adams and Chittenden (see Fig.10 A test cell containing a dressing attached to the SIS to seal the defect was connected to Fig.11 Flow system as shown. A FisherScientific FH100M multichannel peristaltic pump with a 13-310-911 flow cassette was used to provide a controlled flow rate of approximately 20 ml / min. Synthetic urine at approximately 34°C-37°C and completely filling the cell volume was flowed through the cell at a flow rate of approximately 20 ml per minute for 6-20 hours. The purpose of this test was to demonstrate the ability of the dressing to remain adhered to the mucosa under flowing urine without tearing or losing particles or larger fragments from the dressing.
[0240] For Type C dressings (Dressing Lots 75 and 80), one test was conducted for 20 hours. At the end of the test, an external pressure of 1:250 v / v blood in standard saline at nearly 20 mmHg was applied through the jacketed loop of the glass test cell to test the adhesion of the test dressing to the tissue. Four pressures were applied, and over a 3 mm diameter hole, the dressing successfully remained adhered to the inner surface of the SIS, resisting the external fluid pressure in all four pressure application situations. The mass loss of the dressings for this 20-hour test was also examined (by comparing the dry weight before and after the test by weight testing). Weight testing of Type C dressings after 20 hours showed that the material loss of catechol-modified deacetylated chitosan (most likely due to dissolution) was ≤15% based on the original dressing dry weight. All other tests on Type C dressings were conducted for 6 hours without the application of external pressure. For Type C dressings, there was no obvious visible dissolution of the dressing or any material loss of the dressing. At the end of the test, all dressings remained adhered to the SIS. The adhesion (to the SIS mucosa) and cohesion of the dressing were moderate.
[0241] For the Type B batches of dressings (Batches 78 and 83), one test was conducted at 24 hours. The dressings for this 24 hour test were examined for mass loss (by gravimetric testing to compare dry weight before and after testing). Gravimetric testing of the Type B dressing after 24 hours showed that material loss (most likely due to dissolution) of the catechol-modified chitosan was significant at 39.4% based on the dry weight of the original dressing. All other tests on the Type B dressing were conducted for 6 hours. For the Type B dressing, there was clear evidence of significant dissolution (gelling) of the dressing and loss of material from the dressing (visible fragments released from the dressing). The adhesion (adhesion to the SIS mucosa) and cohesion of the dressing were rated as moderate to low.
[0242] Example 4.
[0243] Foldability and unfolding testing of dressings
[0244] All dressing batches (N ≥ 3) were tested for foldability, as this is an important feature of the ability to attach, roll and unfold dressings formed from the materials of the present invention to prostate and bladder neck lesions. The folding test involves first folding the final compressed circular dressing in a horizontal plane through 180° edge to edge in a counterclockwise direction, holding the edges together, and then compressing firmly in the middle of the dressing to create a single linear fold axis (or crease) in the dressing. The folded dressing is then opened and the edge-to-edge fold is reproduced on a new fold axis, but in the opposite clockwise direction. Successful foldability is evaluated by the absence of any visible rips or cracks along the fold axis and the absence of an appreciable loss in the tensile properties of the dressing (determined by gently pulling on the fold of the dressing). The test results for foldability are as follows: Fig.15 as shown in column 4 of .
[0245] The preferred chitosan-backed A, B, and C dressings were deployed and tested (N=5) using a 250-mL volumetric flask filled with saline as a urine-filled bladder neck model. The fully assembled device with CEHD dressing, sheath, and balloon catheter (distal balloon and proximal balloon) was immersed in saline below the neck of the volumetric flask. The CEHD application was initiated by inflating the distal balloon to break the waterproof protective sheath at its distal end, and then the distal balloon was quickly positioned to the bladder neck by pulling its dry free end to the outside of the flask. The torn sheath was manually removed and completely, followed by rapid and smooth inflation of the proximal balloon to open and adhere the dressing near the neck of the flask. All dressing types (A, B, and C) were successfully delivered and had good adhesion to the neck of the glass container.
[0246] Example 5.
[0247] Biocompatibility of dressing types
[0248] Finished, packaged, sterile (25 kGy terminal gamma) devices were tested for biocompatibility per ISO 10993-1 according to the testing requirements for external communication devices with indirect blood access for limited contact. Testing included cytotoxicity, skin irritation, and acute systemic toxicity (each test performed in triplicate).
[0249] Type A and C dressings passed all biocompatibility tests, whereas Type B dressing failed the acute systemic toxicity test. It is suspected that gamma irradiation produced cytotoxic sulfhydryl residues in Type B dressing.
[0250] Example 6.
[0251] Acute in vivo bladder neck and swine splenic capsular stripping models of hemostasis
[0252] Acute in vivo testing was performed in 6 female livestock Yorkshire pigs weighing 40-50 Kg (Oak Hill Genetics, CA) and the delivery device was assembled with three CEHD prototypes (Dressing A: n=6; Dressing B: n=9; Dressing C: n=10). The experiment was designed as a blinded, randomized study of the efficacy of a single prototype versus control in an acute porcine bladder neck and spleen parenchymal hemorrhagic injury model.
[0253] Table 2.
[0254] Acute in vivo study results
[0255]
[0256]
[0257] * Dressing C was selected for the 7-day survival study.
[0258] 0, 1, 2, 3 and 4 = None (material does not adhere), Low (adheres, but falls off easily), Moderate (can be removed by probing at edge), Moderate to Strong (prevents removal by probing at edge) and Strong (probe cannot remove edge) adhesion, respectively.
[0259] Surgical gauze was used as a negative control for the spleen injury model.
[0260] Examples 7-11.
[0261] Examples 7-11 relate to CGHD chitosan dressings.
[0262] The following materials were used in CGHD research and development:
[0263] Chitosan A: Primex ChitoClear 65010, TM 4375, MW = 250-300 kDa, Brookfield viscosity of 1.0% w / w chitosan solution in 1.0% acetic acid at 25 ° C and spindle LV1 = 390 cPs, DDA = 80% (by colloid titration).
[0264] Chitosan B: Primex ChitoClear 43000, TM 4167, MW = 110-150 kDa, Brookfield viscosity of 1.0% w / w chitosan solution in 1.0% acetic acid at 25 ° C and spindle LV1 = 9 cPs, DDA = 95% (by colloid titration).
[0265] Glacial acetic acid: Fisher Scientific, catalog number A38-212.
[0266] Hydrochloric acid: 1.0 M aqueous solution Sigma Aldrich, catalog number H9892.
[0267] L-Lactic acid: JT Baker, catalog number 0196-01.
[0268] Glycolic acid: JT Baker, catalog number M821-05.
[0269] Sodium hydroxide: 5.0 M NaOH aqueous solution Sigma Aldrich, catalog number S8263-150 ml.
[0270] Potassium hydroxide: 0.1M KOH in methanol (BDH).
[0271] Ethanol: 200° Proof Sigma Aldrich, catalog number 459844-1L.
[0272] Microfibrous chitin: 100% acetylated, aspect ratio -100 / 1, -10 micron diameter.
[0273] Weifang
[0274] Basis weight 12g / m 2 Centrifugal spin of chitosan nanofibers batch number G01
[0275] Tricol medical grade nonwoven microfiber.
[0276] Deionized water: Ricca ACS reagent grade deionized water, catalog number 9152-5.
[0277] Acetic anhydride: ACS reagent grade from Sigman Aldrich, catalog number 320102-1L.
[0278] 3,4-Dihydroxyhydrocinnamic acid (Mw = 182.17 g / mo): 98% Sigma Aldrich, catalog number 102601.
[0279] 1-Ethyl-3-(-3-dimethylamino-propyl)-carbodiimide: (or N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride, with the conventional letter abbreviation EDC) Sigma Aldrich, catalog number E7750.
[0280] Sodium chloride: Sigma Aldrich, catalog number 793566-500g.
[0281] Synthetic gastric juice: Pepsin-Sigma Aldrich P7000-25G, NaCl-Sigma Aldrich 793566-500G, H2O ACS reagent grade, NaOH-Sigma Aldrich, catalog number S8263-150ml.
[0282] Tissue: Fresh porcine bladder mucosa, fresh porcine gastric mucosa from Animal Biotech Industries Inc.
[0283] Citrated whole blood: Lampire Biological Laboratory Bovine CPD, catalog number 7720010.
[0284] Cyanoacrylate: Permabond 910 Tissue Adhesive, catalog number 72590.
[0285] Dialysis tubing: 3,500Da MWCO Snakeskin dialysis tubing (Fisher Scientific), catalog number PI88244.
[0286] Pectin: MP Biomedicals LLC, catalog number 102587.
[0287] Glycerol: Sigma Aldrich, catalog number G-8773.
[0288] Polyethylene glycol: Spectrum, catalog number PO108.
[0289] Polyethylene oxide: Mw 400,000 Da, Sigma Aldrich catalog number 372773-500G.
[0290] Bloxam 407: Spectrum, catalog number P1166.
[0291] Guar gum: Sigma Aldrich, catalog number G4129.
[0292] Cellulose (microcrystalline powder): Sigma Aldrich, catalog number 435236.
[0293] Polyacrylic acid: Mv 1,250,000 Sigma Aldrich, catalog number 306215-100G.
[0294] HemCon Pro, a highly effective commercial chitosan hemostatic dressing, was used as a control dressing in the positive acute hemostasis study.
[0295] In the acute hemostasis studies, standard surgical gauze was used as a negative control.
[0296] Example 7
[0297] Preparation and Characterization of Catechol Chitosan
[0298] Method 1.
[0299] Chitosan A (9.0 g) was dissolved in deionized water (148 g) and HCl (28 ml, 1.0 M HCl). A 1:1 (150 ml) water:ethanol solution was prepared. 3,4-Dihydroxyhydrocinnamic acid (25.9 mmol) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (51.8 mmol) were dissolved in the water / alcohol solution. The water / alcohol solution was added to the chitosan solution. The solution was mixed vigorously. The pH of the reaction mixture was controlled to 5.4 using dropwise addition of 0.1 M HCl and 0.1 NaOH solutions and reacted for at least 12 hours with overhead stirring. Thereafter, the chitosan solution (~300 ml) was dialyzed against 5 liters of water acidified with 1 drop of 1.0 M HCl solution for 6 days and then dialyzed against non-acidified water for at least 3 hours. The dialysate was changed every ~24 hours throughout the dialysis process, with at least 5 water changes.
[0300] Method 2
[0301] Chitosan A (1.5 g) was dissolved in water (140 g) and HCl (5 ml, 1.0 M HCl). A 1:1 solution of water:ethanol (145 ml) was prepared. 3,4-Dihydroxyhydrocinnamic acid (10.5 mmol) and N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (13.0 mmol) were dissolved in the water / alcohol solution. The water / alcohol solution was slowly added to the chitosan solution and the reaction mixture was stirred at a low stirrer speed using an overhead mechanical stirrer. The reaction mixture was controlled to pH 5.5 by dropwise addition of 0.1 M NaOH and 0.1 M NaOH solutions and reacted for ~12 hours with stirring. After the reaction process, the solution was dialyzed as described in Method 1.
[0302] Method 3
[0303] Chitosan A (9.0 g) was dissolved in water (126 g) acidified with HCl (30 ml, 1.0 M). A 1:1 water:ethanol solution (150 ml) was prepared with N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (31.3 mmol) dissolved in a water / alcohol solution. Thereafter, 3,4-dihydroxyhydrocinnamic acid (15.7 mmol) was dissolved in 15 ml of water and the solution was slowly added to the chitosan solution with overhead mechanical stirring. The water / alcohol solution containing N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride was slowly added to the chitosan solution and the reaction mixture was stirred with an overhead mechanical stirrer at a low stirrer speed. The reaction mixture was controlled to pH 5.5 using dropwise addition of 0.1 M KOH (methanol solution) and 0.1 M HCl solution and the reaction was maintained with stirring for ~12 hours. After the reaction process, the solution was dialyzed as described in Method 1.
[0304] Method 4
[0305] Chitosan A (9.0 g) was dissolved in water (126 g) acidified with hydrochloric acid (30 ml, 1.0 M). The solution was then adjusted to a pH close to 5.1 using 0.1 M HCl and 0.1 M NaOH aqueous solution. A 1:1 water:ethanol solution (150 ml) was prepared using N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride (31.3 mmol) dissolved in a water / alcohol solution. Thereafter, 3,4-dihydroxyhydrocinnamic acid (15.7 mmol) was dissolved in 15 ml of water and the solution was slowly added to the chitosan solution under moderate overhead mechanical stirring. The water / alcohol solution containing N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride was slowly added to the chitosan solution and the reaction mixture was stirred at a low stirrer speed using an overhead mechanical stirrer. The reaction mixture was controlled to pH 5.0 using dropwise addition of 0.1 M KOH (methanolic solution) and 0.1 M HCl solution and the reaction was maintained under stirring for ~12 hours. After the reaction process, the solution was dialyzed as described in Method 1.
[0306] Degree of substitution of catechol chitosan
[0307] A quartz UV test cell (path length 1 cm, x2 (HACH Co., catalog number 48228-00) was used to acquire UV / vis spectra. The UV / Vis spectrophotometer was a Varian Cary Bio 100.
[0308] A standard solution of 3,4-dihydroxyhydrocinnamic acid was prepared in water and the absorbance at 280 nm was plotted against the concentration. The extinction coefficient ε in the Beer Lambert correlation for the absorbance in the dilute solution is shown below
[0309] A=ε·c·l
[0310] A is the absorbance (dimensionless), and l is the path length.
[0311] (absorbance < 0.5) was determined to be 2,540 ± 50 liter / (mol.cm). This value was used to determine the degree of substitution in the modified chitosan in a known mass of a modified chitosan dilute aqueous solution, a known volume of solution and the peak absorbance measured at 280 nm.
[0312] Dilute the chitosan-catechol solution so that its absorbance at 280 nm is less than 0.5 (usually about 1:50 or 1:100). Use the absorbance, the weight of the solution used in the dilution, and the percent solids (CS-catechol) to determine the fractional substitution (f) of HCA relative to the free amines on the chitosan backbone according to the following equation: DS ):-
[0313]
[0314] Where A is the UV / vis absorbance of the modified chitosan at 280 nm; V is the volume (liters) of the modified chitosan solution obtained after drying to a constant dry mass; m CC is the measured dry mass of catechol-modified chitosan (g); f DDA is the fraction of the degree of deacetylation of chitosan.
[0315] result
[0316] Chitosan-catechol synthesis can produce 50-300 mL chitosan-catechol solutions ranging from milky white to transparent, from light pink to brown, and with viscosities ranging from thin liquid consistency (e.g., water with a viscosity close to 1 cps) to thick liquid consistency (e.g., honey: viscosity >100,000 cps). The synthesis results (see Table 1) depend on the initial concentration of chitosan, avoiding precipitation of chitosan during the pH adjustment step from close to pH 2 to pH 5, maintaining the pH at 5.0-5.5 during the reaction, and thoroughly removing low molecular weight components in the dialysis wash step.
[0317] Table 3.
[0318] Overview of Characterization Results
[0319]
[0320] Determine the percentage of dry solids in a solution by gravimetric analysis
[0321] *The synthesis in method 2 resulted in too high Uv / vis absorbance in the degree of substitution determination
[0322] Concentration of catechol chitosan by removing water from a solution suspended in a dialysis membrane by heat-assisted drying
[0323] Example 8.
[0324] Hydrophilic polymer dressing with frozen phase separation
[0325] An aqueous hydrophilic polymer solution was prepared in a 500 ml, 1000 ml or 2000 ml Nalgene LDPE bottle or polypropylene beaker by adding ingredients including, but not limited to, previously prepared solutions, hydrophilic polymer, water, acid and other ingredients. Figures 17A-17C The formulation method, hydrophilic polymer and % w / w of the hydrophilic polymer component of the solution are listed. Figures 17A-17C Some formulations in the Figures 17A-17C The strategies are listed as A, B, C, D, E, F and G. Strategy A is mainly used as a control for materials (such as deacetylated chitosan) that are not expected to resist dissolution in the stomach by in vitro simulated gastrointestinal fluid testing. Reacetylation (Strategy B) is one of the proposed strategies to reduce the dissolution / degradation rate until in vitro simulated gastrointestinal fluid testing in the presence of pepsin showed that the degradation and dissolution rate of deacetylated chitosan was faster with a lower degree of deacetylation. Strategy C is to study the composition of known polysaccharides (guar gum, pectin and starch) without deacetylated chitosan, which can resist in vitro simulated gastrointestinal fluid digestion. Strategy D is Strategy C using chitosan and other possible hydrophilic polymers. Strategy E is to use catechol-modified chitosan as the only hydrophilic polymer. Strategy F is to use catechol-modified chitosan with other hydrophilic polymers. Strategy G is to use centrifugal spun chitosan fibers.
[0326] The major problems encountered when formulating a dressing for gastrointestinal hemostatic administration were: (1) unexpected and rapid (<10 min) degradation of chitin and chitosan by pepsin in synthetic gastric fluid, with pepsin accelerating the degradation rate of chitosan at an increasing rate equivalent to that of low degrees of deacetylation; (2) unexpected interference from blood in achieving adhesion with pure catechol-modified chitosan; and (3) susceptibility to dressing rupture and tearing when reformulating to address other issues.
[0327] The final hydrophilic polymer solution % w / w was between 0.1%-4% polymer. The capped bottles and their contents were continuously mixed at room temperature for 12-24 hours using an IKA KS260 orbital oscillator or a Wheaton benchtop bottle roller to achieve complete solution homogeneity. The beaker solution was mixed on a magnetic stirring plate with magnetic stirring beads at room temperature for 12-24 hours to achieve solution homogeneity. During the mixing process, the beaker was isolated from the external environment using a sealing film. When there was no suspension condition (except A06, B02, B04 and C05), the solution prepared for frozen phase separation was basically uniform and clear. The catechol deacetylated chitosan solution showed some turbidity and milky appearance, indicating the presence of some dispersed fine catechol deacetylated chitosan spherical particles.
[0328] Except for the case of Strategy G, chitosan solutions were prepared as frozen phase-separated dressings, wherein the weight percent of hydrophilic polymer in the final solution was 0.25%-4% w / w aqueous solution. The frozen phase separation was carried out in a Teflon-coated aluminum mold well with a horizontal flat bottom. The solution was poured into the well to a height of preferably no more than about 10 mm, more preferably 2.5 mm, and most preferably 5.0 mm from the bottom of the mold. Cooling was applied through the bottom of the mold to the solution in the mold, which was initially at a temperature between 15°C and 30°C before freezing, and then frozen. Although other cooling temperatures may be applied to achieve a suitable frozen phase-separated structure, it is preferred that the cooling temperature applied to the shelf is -40°C, more preferably -55°C, and most preferably -45°C. After the solution reaches frozen phase separation and the temperature of the frozen solution reaches equilibrium at the freezing temperature, the system is further frozen phase separated and re-equilibrated for at least 1 hour before drying. In an improved method of freezing and mold filling to accommodate different layers of frozen phase-separated solutions, the first layer is added to the mold to a preferred depth and frozen, then the second layer is added and frozen, and then a multi-layer frozen phase-separated dressing is prepared in this way. Care should be taken to ensure that there is no frost between the (n-1)th frozen solution and the nth poured solution, and the difference in the frozen structure between the layers may cause cracking. During this research, the discovery of a successful method for layering and adhering a single layer of pre-freeze-dried hydrophilic polymer matrix to a single co-adhered compressed multi-layer composite sheet was an unexpected and important discovery. It is also possible to use compression to combine freeze-dried compositions prepared separately.
[0329] The frozen phase-separated frozen solution patches were subjected to sublimation freeze drying using a 24 square foot Virtis Benchmark 2000 pilot-scale freeze dryer. In the primary freeze drying (removal of ice that is not hydrogen bonded to the hydrophilic polymer), the frozen patches equilibrated in their molds were depressurized to ≤300 mTorr in the freeze dryer, the freeze dryer condenser was set to ≤-65°C, and the freeze dryer shelf was heated to promote sublimation of ice from the frozen separated patches without raising the patch temperature above -15°C. After essentially all unbound ice was removed, the shelf temperature was raised to nearly 25°C to remove hydrogen-bound ice and reduce the moisture content in the dry dressing to no more than about 4% residual water in the dry dressing. The final dried matrix conformed to the original shape of the filled mold, with its length and width shrinking by nearly 5%, and a density of 0.005 g / cm 3 -0.04g / cm 3 They contain more than 95% void space and are interconnected porous structures (eg, 20-300 microns) with fine polymer layers (eg, submicron to 5 micron thickness) and pore spacings between adjacent layers of, eg, 20 microns to 300 microns.
[0330] After freezing phase separation and drying, the dried matrix is compressed from its original thickness (10mm-2.5mm) to a final thickness preferably close to 50 microns. If two uncompressed dressings are compressed in a manner one on top of the other, they will be permanently bonded together at the end of the compression process. A calibrated thin shim of uniform thickness can be used in compression to achieve the desired compression dressing thickness, which is substantially the same as the shim thickness. There are a variety of methods to achieve this compression, wherein the desired compression is close to 50 microns. The preferred compression method used in this study is to compress the entire dry uncompressed dressing (size typically close to 100mm long x100mm wide x 2.5mm high or 50mm diameter x 2.5mm high), wherein the uniaxial compression rate is ≤10mm / min or approximately ≤0.5mm / min, and the thickness between the aligned press plates should be close to ≤100 micron thickness. Although lower compression rates lead to better mechanical properties of the final dressing, it is acceptable to prepare a dressing close to, for example, about 10mm / min with an initial compression rate. The press plate (Teflon coated Mic 6 aluminum 300mm x 300mm x 90mm) was machined to a flat surface (≤ 5 microns in 300mm). During compression, the temperature of the press plate was preferably maintained near 80°C for 3 to 5 minutes of uniaxial compression. Compression was achieved by screw loading at the four corners of the press plate with a maximum load of four tons (tons means 1000kg) at each corner. Compression was continued for at least 2 minutes before releasing the load. The compressed thickness and weight of the novel compressed hydrophilic polymer matrix were measured. The final density was between 0.35-0.55 g / cm3 After compression, the dressing was further processed. This additional processing included die cutting into 2.5 cm diameter test pieces and in some cases thermal annealing heat treatment (heating in a convection oven at 60°C-150°C for 5-30 minutes). At the end of processing, the dressing was placed in a foil bag with a heat seal. The packaged dressings for animal and biocompatibility testing were irradiated with 25 kGy gamma rays.
[0331] Example 9.
[0332] In vitro testing of a prototype gastrointestinal hemostatic dressing
[0333] Synthetic gastric juice preparation: Pepsin (1.6 g), NaCl (1 g), water (500 ml) were added to a 1000 ml Nalgene LDPE bottle and mixed. Acidity was adjusted to pH 3-4 using Millipore pH 0-14 universal indicator strips and 3.0 M HCl was added dropwise. If necessary, 1.0 M NaOH was added dropwise to increase pH.
[0334] 1. Test tube method
[0335] To quickly screen the resistance of the test article to dissolution / fragmentation in synthetic gastric fluid, a 0.5 cm x 0.5 cm piece of the test article was added to the bottom of a labeled 15 ml Falcon tube, 5 ml of gastric fluid was added to the tube, which was then covered and placed vertically in an incubator at 37° C. with gentle shaking. The test tube was monitored until the sample was observed to show dissolution / fragmentation, and the time of dissolution / fragmentation was recorded. Figures 16A-16C Results of in vitro tests were provided.
[0336] 2. Beaker method
[0337] For the material that shows resistance in the test tube test, a kind of improved test method is developed, wherein the fresh gastric mucosa sheet of 38mmx 38mm is adhered to the bottom in the polystyrene beaker (250ml, Fisher catalog number 08-732-124) of the thin layer of cyanoacrylate adhesive smeared with cotton swab.The mucosal surface before gluing is wiped dry using Texwipe paper towel.The adhesive is dried for 2-5 minutes.After being adhered to the beaker completely, the exposed top tissue surface is wetted dropwise (usually 2 drops) with the whole ox blood of citric acidification, and the load of 500g orthogonal to the mucosal surface is applied to the 20mm x 20mm sheet from the test article for 1 minute that blood covers.Synthetic gastric juice (~90ml) at room temperature is added in the beaker. The beaker was sealed with parafilm and placed upright on an IKA KS260 orbital shaker in an incubator at 37° C. with gentle shaking (130 rpm). The interior of the beaker was monitored every minute and then every hour until clear separation from the mucosa and / or dissolution / fragmentation of the sample was observed, and the time of separation / dissolution / fragmentation was recorded.
[0338] During the test method development process, the applied load (up to 5 kg) and the application time of the attachment were up to 5 minutes. In contrast to minimally invasive in vivo applications, the gastrointestinal surgical team recommended that a load of no more than 300 g be applied uniformly over a 2.5 cm diameter dressing for no more than 30 seconds. The original conditions of 5 kg and 120 seconds were modified to 500 g for 1 minute. The application of a 300 g load for 30 seconds is now applied. Beaker test results are shown in Figure 2. Figures 16A-16C as shown in .
[0339] 3. Mechanical folding test
[0340] The sample sheet was folded 180° along the length and width axis, and the indentation line was compressed. The dry test sheet (25 mm x 25 mm) was folded and unfolded, and its tear and crack resistance were recorded. The folding test results are shown in Figures 16A-16C as shown in .
[0341] 4. Mechanical Tissue Adhesion
[0342] A uniaxial mechanical tester (Instron model 5844) with a 10N load cell was used to study wet adhesion to the mucosa. Adhesion testing was performed using ASTM F2258-03 "Standard Test Method for Strength: Tensile Properties of Tissue Adhesives". The test configuration was used to uniaxially align the lower and upper PVC probes in the z vertical direction so that the edges of the 15.2mm diameter surfaces of the xy level could accurately (± 0.2mm) coincide with each other in the case of uniaxial reduction, with the top probe uniaxially reduced, which was supported on the upper movable Instron crosshead in the chuck fixture. The lower PVC probe was supported in a fixed bottom chuck fixture. Before testing the PVC surface with cyanoacrylate glue, the bottom PVC horizontal surface was used to support a 10mm x 10mm mucosal tissue sample adhered for at least 5 minutes. The top PVC horizontal surface was used to support a 10mm x 10mm CGHD test piece, which was bonded with 3M double-sided tape at least 5 minutes before testing. Before lowering the probe onto the test surface, the square tissue block was wetted with 0.25 ml of decitrated bovine whole blood CPD. The probe was lowered at a rate of 10 mm / min until a maximum load of 0.98 N was reached. Upon contact, the test piece and tissue piece were in precise contact (± 0.2 mm) and coplanar with each other. The uniaxial probe load of 0.98 N was maintained for 30 seconds, after which the probe was removed at a rate of 10 mm / min and the maximum failure stress was recorded. The results of the adhesion test are shown in Table 4.
[0343] Table 4.
[0344] Probe attachment results
[0345]
[0346] Example 10.
[0347] In vivo (porcine upper gastrointestinal bleeding model) screening study
[0348] animal
[0349] A total of 4 crossbred adult domestic pigs weighing 40-50 kg were used in this study.
[0350] All experiments were performed in accordance with the 2011 National Research Council, “Guide for the Care and Use of Laboratory Animals” and applicable federal regulations. The animal protocol complied with the NIH Guidelines for the Care and Use of Laboratory Animals and was approved by the Institutional Animal Care and Use Committee. All manipulations and care of animals were performed in an approved animal research facility.
[0351] All animals were examined by veterinary staff to ensure baseline health. Animals were removed from all sleeping quarters 72 hours prior to surgery and no food was allowed 24 hours prior to surgery. Animals were allowed to drink water ad libitum. Twenty minutes prior to surgery, animals were given a 500 mg intravenous bolus of cefotetan and 250 ml of Ringer's lactate fluid. Anesthesia was induced by mask with 5% isoflurane before co-administration of 10% sham-treated pigs (Fort Dodge Laboratories, Fort Dodge, IA). The pigs were intubated, placed on a ventilator, and maintained on 2-3% isoflurane via an endotracheal tube. The right femoral artery was surgically isolated and cannulated with a 6Fr catheter to facilitate continuous blood pressure monitoring and blood recovery for laboratory studies. To induce a coagulopathy state, 5000 units of heparin were given intravenously (IV). Anticoagulation was maintained by continuous infusion of 50 units / kg of heparin during surgery. Activated clotting time (ACT) levels were tested after 10 minutes and then every 20 minutes during surgery as needed with additional IV-administered heparin (50% of the initial dose, 2500 units) to maintain ACT>250 seconds of anticoagulation. ECG, blood pressure, and oxygen saturation were monitored during surgery and recovery. Vital data including blood pressure, isoflurane %, O2 flow, respiratory rate, heart rate, SpO2, capillary refill time, blood pressure and mean arterial pressure, and body temperature were recorded every 15 minutes.
[0352] At the completion of the experiment, the animals were euthanized by IV administration of Euthasol (1 mg / 10 lbs) under anesthesia. Death was confirmed by the absence of a heartbeat by flat-wave ECG and stethoscope findings.
[0353] Gastric bleeding model
[0354] The pig was prepared with chlorhexidine and draped in a sterile manner. A midline laparotomy was performed to expose the stomach. A 5-cm segment of the upper gastric muscle vessels was dissected from the gastric wall. For each segment, a 1-cm gastrotomy was performed near the free but intact vessels. The artery was then pushed through the gastrotomy and positioned to expose it to the gastric cavity. The gastric incision was then closed together with the abdominal wall in a standard manner. An upper endoscopy (GIF Q180 model, Olympus) was performed to identify the gastric wound site in the stomach. The wound site and gastric vessels were then located and incised with endoscopic biopsy forceps to produce pulsatile bleeding.
[0355] The chitosan gastrointestinal hemostatic dressing (CGHD) identified in Table 5 below was applied manually. In brief, an incision of about 12 cm was made on the anterior gastric wall to expose the gastric cavity and a CGHD prototype dressing (20 mm x 20 mm) was applied to the site of gastric bleeding. Before the dressing was applied, a dry pre-weighed folded gauze sponge was used to absorb any blood from the wound within 15 seconds and weighed, and multiplied by (x) 4 to calculate the bleeding rate (blood weight) per minute. The CGHD dressing was placed over the wound and covered with a gauze sponge. Under a light pressure of nearly 200–300 g, manual pressure was evenly applied to the patch for 30 seconds. At 30 seconds, the gauze was removed and the initial hemostasis of the area was observed, and then signs of rebleeding were observed for up to 10 minutes. After the application was completed, the CGHD dressing was removed and the adhesion of the dressing tissue was ranked according to the adhesion score according to how the dressing was adhered to the tissue surface using the adhesion scoring system (Table 5).
[0356] Table 5:
[0357] Adhesion score
[0358]
[0359] result
[0360]
[0361] In a gastrovascular injury model, three CGHD family prototypes (D24, F11 and G01) showed good hemostatic performance in terms of immediate hemostasis and acceptable adhesion scores. The slow adhesion of pure catechol-modified chitosan to wound tissue was resolved by combining unmodified chitosan with catechol chitosan. A final heat treatment of these compressed frozen phase separation dressings at a temperature close to 80°C for 15 to 30 minutes resulted in a dressing with good immediate tissue adhesion and thus the potential for rapid hemostatic performance in controlling pulsatile bleeding gastrointestinal bleeding under short (30 seconds) low pressure application. It should be noted that Patch Pro is not suitable for endoscopic delivery because it cannot be folded as required and is too thick. In addition, Patch Pro is formed from standard chitosan, which degrades in the upper gastrointestinal tract within about 15 minutes or less.
[0362] Example 11.
[0363] In vivo (Porcine Upper Gastrointestinal Bleeding Model) 3-hour study
[0364] animal
[0365] A total of 4 crossbred adult domestic pigs weighing 40-50 kg were used in this study.
[0366] Animal preparation, surgical preparation, animal anesthesia and animal sacrifice were the same as presented in Example 4.
[0367] Gastric bleeding model
[0368] The pig was prepared with chlorhexidine and draped in a sterile manner. A midline laparotomy was performed to expose the stomach. A 5-cm segment of the suprastomachic vascular muscle was dissected from the gastric wall. For each segment, a 1-cm gastrotomy was performed adjacent to the free but intact vessels. The artery was then pushed through the gastrotomy and positioned to expose it to the gastric lumen. The gastric incision was then closed together with the abdominal wall in a standard manner ( Figure 2). An incision of about 12 cm is cut on the anterior gastric wall to expose the gastric cavity. The wound site and gastric blood vessels are then located and incised with forceps to produce pulsatile bleeding. Before application, the bleeding rate of the absorbent dressing is determined using a pre-measured folded gauze sponge to absorb any blood on the wound for 15 seconds, then weighed and multiplied by x 4 to calculate the bleeding rate. The CGHD dressing is then placed above the bleeding wound and covered with a gauze sponge. Manually apply pressure evenly to the patch for 30 seconds. At 30 seconds, remove the gauze and observe whether the area initially stops bleeding and for up to 10 minutes. After observing for 10 minutes, if hemostasis is achieved, the gastric incision is closed in a layered manner, that is, the surgeon sutures the incised layers together continuously. The abdominal wall is then closed for 3-hour observation. After 3 hours of application, an upper endoscopy (GIF Q180 type, Olympus) is performed to identify the wound dressing for visual inspection. The incisions in the abdomen and stomach are then reopened to perform an overall inspection of the dressing. The CGHD dressings were removed and given an adhesion score based on how well the dressing adhered to the tissue surface using the adhesion scoring system (Table 5).
[0369] After these operations were completed, the wound site was re-prepared by removing the old blood clot and remnants of the wound dressing for reapplication of the second set of dressings as described above. During this phase of the study, each wound site was used to test 2 dressings.
[0370] Bleeding rate
[0371] A hemi-transected vascular injury was made at the gastric vessels using Metzenbaum scissors to produce pulsatile bleeding. The bleeding rate was measured with pre-weighed gauze and recorded in g / min. The bleeding rate for each injury was determined and recorded prior to application of the dressing.
[0372] The test piece is 20mm x 20mm.
[0373] Eight dressings from each type of nanospun chitosan (G01) and chitosan-catechol compound (F11) were tested.
[0374] Application of test pieces
[0375] When the test piece is placed centrally on the injury and sufficient pressure is applied with the fingers to stop the bleeding, the 30-second timer is started. A 50mm x 50mm gauze is folded in half and applied to the 20mm x 20mm test piece. All the blood that subsequently collects is aspirated from the site. After 30 seconds of light pressure (a load close to 300g), the fingers are removed and the test dressing is observed for signs of bleeding. If bleeding is observed, pressure is reapplied for 30 seconds. If hemostasis is achieved after releasing the pressure, the dressing is observed for 10 minutes. If there is no recurrence of bleeding, the gastric wall is closed and observed for 3 hours through a GI scope. If there is no recurrence of bleeding after 3 hours, the dressing test piece is considered successful. If bleeding recurs within 5 minutes, the dressing should be removed and a new dressing should be used. A maximum of two repeated applications are used.
[0376] Table 6:
[0377] The results of this study are summarized below.
[0378]
[0379] *1 Dressings from each group had an additional dressing to stop exudate after the third application of pressure
[0380] **1 Keep the dressing on for an additional 30 seconds
[0381] The nanospun chitosan dressing (G01) was successfully applied in 4 of the 12 dressings applied. The 25% catechol / 75% 2% chitosan dressing (F11) was successfully applied in 6 of the 13 dressings tested. For the application of the dressings, there were two deviations: 1 dressing from each group had an additional dressing to stop exudation, which did not stop on pig #4; while one of the nanospun chitosan dressings could be kept on for an additional 30 seconds.
[0382] In all applications, an endoscope was inserted to assess if the dressing was still in place and hemostasis was achieved. In all cases, all dressings were confirmed to be present, hemostasis, and visible throughout. After more than 3 hours of dressing application, the stomach was opened to inspect the site of injury and to inspect the dressing. All dressings were intact. Clot formation was observed on all wounds. It was noted that in all cases where the initial dressing was successful, no subsequent bleeding from the wound was observed at the 3 hour time point.
[0383] The final optimal dressing prototypes identified through testing in Examples 3, 4 and 5 showed prolonged efficacy once they adhered under gentle manual pressure and maintained for a short period of time required for delivery through a standard gastroscope delivery port. The optimal dressing developed was easily folded (or rolled) in a configuration to be delivered through the standard diameter delivery channel of a standard gastroscope of 2.8 mm.
[0384] All CGHD dressings that achieved successful hemostasis (complete hemostasis) within 10 minutes of initial application and no more than 3 x 30 seconds of application maintained complete hemostasis over a 3 hour test period in a closed porcine stomach. Success was achieved for 31% of G01 prototype applications and 46% of F11 prototype applications. The challenge of this study resulted in a clinically relevant success rate approaching 50% (i.e., the F11 prototype), especially when it is noted that all initially successful mucoadhesive applications produced 100% long-term success. The mixed chitosan and catechol chitosan dressings provide significant resistance to digestion by digestive juices, can be folded / rolled into the most complex and compact form, and provide good adhesive properties when mixed with unmodified chitosan.
[0385] References
[0386] The following is a list of references listed by number and corresponding to the numbers in parentheses noted throughout this specification.
[0387] 1.HCUP,Outcomes by 153Gastrointestinal hemorrhage,in USDepartment of Health and Human / HCUPnet2014,USDepartment of Health and Human Services:Washington DC.
[0388] 2.Rockey, DC, Gastrointestinal bleeding. Gastroenterol Clin North Am, 2005.34(4):p.581-8.
[0389] 3. Crooks, CJ, West, J. and Card, TR, Upper gastrointestinal haemorrhage and deprivation: a nationwide cohort study of health inequality in hospital admissions. Gut, 2012.61(4):p.514-20.
[0390] 4.Jairath,V.,Kahan,B.C.,Logan,R.F.,Hearnshaw,S.A.,Travis,S.P.,Murphy,M.F.and Palmer,K.R.,Mortality from acute upper gastrointestinal bleeding inthe United kingdom:does it display a“weekend effect”?Am J Gastroenterol,2011.106(9):p.1621-8.
[0391] 5.Sung,J.J.,Tsoi,K.K.,Ma,T.K.,Yung,M.Y.,Lau,J.Y.and Chiu,P.W.,Causesof mortality in patients with peptic ulcer bleeding:a prospective cohortstudy of 10,428 cases.Am J Gastroenterol,2010.105(1):p.84-9.
[0392] 6.Jairath,V.,Kahan,B.C.,Stanworth,S.J.,Logan,R.F.,Hearnshaw,S.A.,Travis,S.P.,Palmer,K.R.and Murphy,M.F.,Prevalence,management,and outcomes ofpatients with coagulopathy after acute nonvariceal upper gastrointestinalbleeding in the United Kingdom.Transfusion,2013.53(5):p.1069-76.
[0393] 7.Elta,G.H.,Approach to the patient with gross gastrointestinalbleeding.Textbook of Gastroenterology,2003.In:Yamada T.,Alper,D.H.,Editors(Lippincott Williams and Wilkins):p.698-723.
[0394] 8.Boonpongmanee,S.,Fleischer,D.E.,Pezzullo,J.C.,Collier,K.,Mayoral,W.,Al-Kawas,F.,Chutkan,R.,Lewis,J.H.,Tio,T.L.and Benjamin,S.B.,The frequencyof peptic ulcer as a cause of upper-GI bleeding is exaggerated.GastrointestEndosc,2004.59(7):p.788-94.
[0395] 9.Jairath,V.,Martel,M.,Logan,R.F.and Barkun,A.N.,Why do mortalityrates for nonvariceal upper gastrointestinal bleeding differ around theworld?A systematic review of cohort studies.Can J Gastroenterol,2012.26(8):p.537-43.
[0396] 10.Sheibani,S.,Kim,J.J.,Chen,B.,Park,S.,Saberi,B.,Keyashian,K.,Buxbaum,J.and Laine,L.,Natural history of acute upper GI bleeding due totumours:short-term success and long-term recurrence with or withoutendoscopic therapy.Aliment Pharmacol Ther,2013.38(2):p.144-50.
[0397] 11.Adler,D.G.,Leighton,J.A.,Davila,R.E.,Hirota,W.K.,Jacobson,B.C.,Qureshi,W.A.,Rajan,E.,Zuckerman,M.J.,Fanelli,R.D.,Hambrick,R.D.,Baron,T.andFaigel,D.O.,ASGE guideline:The role of endoscopy in acute non-variceal upper-GI hemorrhage.Gastrointest Endosc,2004.60(4):p.497-504.
[0398] 12.Banerjee,S.,Cash,B.D.,Dominitz,J.A.,Baron,T.H.,Anderson,M.A.,Ben-Menachem,T.,Fisher,L.,Fukami,N.,Harrison,M.E.,Ikenberry,S.O.,Khan,K.,Krinsky,M.L.,Maple,J.,Fanelli,R.D.and Strohmeyer,L.,The role of endoscopy in themanagement of patients with peptic ulcer disease.Gastrointest Endosc,2010.71(4):p.663-8.
[0399] 13.Peng,Y.C.,Chen,S.Y.,Tung,C.F.,Chou,W.K.,Hu,W.H.and Yang,D.Y.,Factors associated with failure of initial endoscopic hemoclip hemostasis forupper gastrointestinal bleeding.J Clin Gastroenterol,2006.40(1):p.25-8.
[0400] 14.Peng,Y.C.,Tung,C.F.,Chow,W.K.,Chen,S.Y.and Chang,C.S.,Factorscontributing to the failure of argon plasma coagulation hemostasis inpatients with nonvariceal upper gastrointestinal tractbleeding.Hepatogastroenterology,2010.57(101):p.781-6.
[0401] 15.Karaman,A.,Baskol,M.,Gursoy,S.,Torun,E.,Yurci,A., M.,Guven,K.,Ozbakir,O.and Yucesoy,M.,Endoscopic topical application of ankaferdblood in gastrointestinal bleeding.Journal of Alternative andComplementary Medicine,2012.18(1):p.65-68.
[0402] 16.Halkerston,K.,Evans,J.,Ismail,D.,Catnach,S.,Chaudhary,R.,Fullard,M.,King,A.and Leahy,A.,PWE-046 Early Clinical Experience of Endoclot TM in theTreatment of Acute Gastro-Intestinal Bleeding.Gut,2013.62(Suppl 1):p.A149.
[0403] 17.Holster,I.L.,Kuipers,E.J.and Tjwa,E.T.T.L.,Hemospray in thetreatment of upper gastrointestinal hemorrhage in patients on antithrombotictherapy.Endoscopy,2013.45(1):p.63-66.
[0404] 18.Sung,J.J.Y.,Luo,D.,Wu,J.C.Y.,Ching,J.Y.L.,Chan,F.K.L.,Lau,J.Y.W.,MacK,S.,Ducharme,R.,Okolo,P.,Canto,M.,Kalloo,A.and Giday,S.A.,Early clinicalexperience of the safety and effectiveness of Hemospray in achievinghemostasis in patients with acute peptic ulcer bleeding.Endoscopy,2011.43(4):p.291-295.
[0405] 19.Yau,A.H.L.,Ou,G.,Galorport,C.,Amar,J.,Bressler,B.,Donnellan,F.,Ko,H.H.,Lam,E and Enns,R.A.,Safety and efficacy of in uppergastrointestinal bleeding.Canadian Journal of Gastroenterology andHepatology,2014.28(2):p.72-76.
[0406] 20.Kheirabadi,B.S.,Mace,J.E.,Terrazas,I.B.,Fedyk,C.G.,Estep,J.S.,Dubick,M.A.and Blackbourne,L.H.,Safety Evaluation of New Hemostatic Agents,Smectite Granules,and Kaolin-Coated Gauze in a Vascular Injury Wound Model inSwine.Journal of Trauma and Acute Care Surgery,2010.68(2):p.269-278.
Claims
1. A chitosan material, wherein the chitosan material is modified with at least one of 3,4-dihydroxyhydrocinnamic acid (hydrogenated caffeic acid), 3,4-dihydroxycinnamic acid (caffeic acid), trans-3,4-dihydroxycinnamic acid (trans-caffeic acid) and 3,4-dihydroxyphenylacetic acid (DOPAC, plateau catechin), and comprises catechol-modified chitosan, wherein the catechol-modified chitosan further comprises catechol oxidized to o-quinone and cross-linked to form at least one of compound (A) or compound (B), wherein the chitosan material is in a dry solid form that resists dissolution when exposed to a biological fluid in the pH 3.0-pH 8.0 range at 37°C within 12 hours prior to administration and completely dissolves from a target tissue site within 7 days, wherein the chitosan material adheres to a tissue surface when the chitosan material is wet with an adhesion strength greater than or equal to 1 kPa, wherein the chitosan material has a thickness of 500 microns or less.
2. The chitosan material of claim 1, wherein the chitosan material has a range of 0.03 g / cm 3 -0.7g / cm 3 density.
3. The chitosan material of claim 2, wherein the chitosan material has a density in the following ranges: (i) 0.3 g / cm 3 -0.4g / cm 3 or (ii) 0.4 g / cm 3 -0.5g / cm 3 .
4. The chitosan material of claim 2, wherein the chitosan material has a g / cm 3 -0.55g / cm 3 density.
5. The chitosan material of claim 1, wherein the chitosan material is compressed.
6. The chitosan material of claim 1, The chitosan material is in the shape of a square, rectangle, circle or annular petals; The length and width of the square or rectangle may each be in the range of: 1) 10-50 mm; or 2) 30 mm-70 mm; and The diameter measurement values of the circular or annular petal shapes are in the range of: a) 10mm-50mm; or 30mm-70mm.
7. The chitosan material of claim 6, wherein the chitosan material measures one of the following: (i) 70 mm x 70 mm; (ii) 50 mm x 50 mm; (iii) 30 mm x 30 mm; (iv) 25 mm x 25 mm; (v) 20 mm x 20 mm; or (vi) 10 mm x 10 mm.
8. The chitosan material of claim 1, wherein the chitosan material has a moisture content of: (1) 15% or less by weight (w / w); (2) 8% or less by weight (w / w); or (3) 4% or less by weight (w / w).
9. The chitosan material of claim 1, wherein the chitosan material has an adherent side and a non-adherent side.
10. The chitosan material of claim 9, wherein the adhesive side is provided on the first layer and the non-adhesive side is provided on the second layer.
11. The chitosan material of claim 9, wherein the adhesive side adheres to a tissue surface when the chitosan material is wet.
12. The chitosan material of claim 9, wherein the non-adherent side does not adhere to the delivery device when the chitosan material is wet.
13. The chitosan material of claim 1, wherein the chitosan material adheres to the gastrointestinal mucosa in 1 minute or less, or adheres to the bladder mucosa in 3 minutes or less, or both.
14. The chitosan material of claim 1, wherein the chitosan material forms a quaternary ammonium cation on the chitosan glucosamine C-2 amine at the tissue site.
15. The chitosan material of claim 1, wherein the chitosan material has a coloration of: 1) brown coloration, including dark brown coloration; or 2) pink to pinkish brown coloration.
16. The chitosan material of claim 1, further comprising a freeze-dried layer.
17. The chitosan material of claim 16, wherein the freeze-dried structure has a thickness of 50 microns or less; or 100 microns or less.
18. The chitosan material of claim 16, wherein the freeze-dried structure comprises more than one freeze-dried layer.
19. The chitosan material of claim 1 further comprising spun fibers.
20. The chitosan material of claim 1, further comprising a porous surface.
21. The chitosan material of claim 20, wherein the porous surface provides one or more of: (i) an absorbent surface; and (ii) channels that redirect moisture away from the target tissue surface site.
22. The chitosan material of claim 1, wherein the chitosan material adheres to wet tissue under wet conditions.
23. The chitosan material of claim 1, wherein the chitosan material resists dissolution in water, saline solution, blood, gastrointestinal fluids, or urine at about 37°C for at least about 6 hours.
24. The chitosan material of claim 1, wherein the chitosan material can be folded or rolled without breaking or tearing.
25. The chitosan material of claim 1, wherein the chitosan material has an outwardly facing surface area in an open, unfolded or unfolded state that is about 8 times, about 7 times, about 6 times, about 5 times, or about 4 times the outwardly facing surface area of the same chitosan material in a closed, rolled or folded state.
26. The chitosan material of claim 1, wherein the chitosan material can be punctured or sewn without rupturing or tearing.
27. The chitosan material of claim 1, wherein the chitosan material is capable of being delivered intact via a balloon device, a wire device, or an endoscopic device.
28. The chitosan material of claim 27, wherein the balloon device or the wire device or the endoscopic device comprises a working channel having a diameter of 3.2 mm or less or 7.0 mm or less, and wherein the chitosan material is delivered through the working channel.
29. The chitosan material of claim 1, wherein the chitosan material is capable of wetting and completely adhering to gastric mucosa in less than 30 seconds, or wetting and adhering to bladder mucosa in less than 3 minutes, or both, under application of light pressure.
30. The chitosan material of claim 29, wherein the light compression is 200-300 g, or the chitosan material is completely adhered to the bladder mucosa in less than 2 minutes, or both.
31. The chitosan material of claim 1, wherein the chitosan material is capable of removing both hydrophilic and hydrophobic biological fluids that would interfere with adhesion.
32. The chitosan material of claim 1, wherein the chitosan material is capable of remaining intact in place and stopping moderate to the following range of oozing blood: 1) 20 ml / min-150 ml / min; or 2) 1 ml / min-150 ml / min.
33. The chitosan material of claim 1, wherein after being adhered to a target tissue site, the chitosan material is readily detachable from a delivery device.
34. The chitosan material of claim 1, wherein the chitosan material resists dissolution for at least 6 hours after being adhered to the site of injury in the presence of a corrosive enzyme and an acidic environment of about pH 3, or in the presence of urine, or both.
35. The chitosan material of claim 1, wherein the chitosan material is capable of occluding and protecting a target tissue site for at least 12 hours.
36. The chitosan material of claim 1, wherein the chitosan material is capable of achieving controlled, slow dissolution from the attachment site.
37. The chitosan material of claim 1, wherein the chitosan material is capable of folding and unfolding.
38. The chitosan material of claim 1, wherein the chitosan material is capable of being rolled and unrolled.
39. The chitosan material of claim 1, wherein the chitosan material is not readily soluble in water, saline solution, blood, or gastrointestinal fluid or bladder fluid or urine at about 37°C for: 1) at least 12 hours after administration; or 2) at least 24 hours after administration.
40. The chitosan material of claim 1, wherein the chitosan material does not adhere to a delivery device.
41. The chitosan material of claim 1, wherein the chitosan material does not increase or decrease in length or width by more than about 25%, or in thickness by more than about 50%, in the presence of water, saline solution, blood, or gastrointestinal fluid or bladder fluid or urine at about 37°C.
42. The chitosan material of claim 1, wherein the chitosan material comprises an adhesive side that interacts with the injury site, and wherein the chitosan material comprises a non-adhesive side that interacts with one of the delivery device or the adhesive side when the chitosan material is in a dry and folded or dry and rolled state.
43. The chitosan material of claim 1, wherein the chitosan material is capable of being terminally sterilized without affecting the properties of the chitosan material.
44. The chitosan material of claim 1, wherein the chitosan material is capable of being stored under controlled conditions over time without affecting the properties of the chitosan material.
45. The chitosan material of claim 1, wherein the dry solid form is a powder.
46. The chitosan material of claim 1, wherein the dry solid form is a matrix.
47. The chitosan material of claim 1, wherein the dry solid form is a film.
48. The chitosan material of claim 1, wherein the dry solid form is a thin layer foil.
49. The chitosan material of claim 1, wherein the dry solid form is pleget.
50. The chitosan material of claim 1, wherein the dry solid form is fibers.
51. The chitosan material of claim 1, wherein the dry solid form is a coating.
52. A method for producing the catechol-modified chitosan material of claim 1, comprising: (a) Synthesis using chitosan and catechol in an aqueous reaction solution; (b) maintaining the pH of the reaction solution at or below pH 5.5; (c) after step (b), increasing the pH of the reaction solution and controlling the exposure of oxygen to the reaction solution to obtain oxidation and crosslinking of the catechol; and (d) drying the reaction solution; The method does not comprise an intermediate drying step between step (b) and step (c).
53. The method of claim 52, wherein in step (c), the pH of the reaction solution is increased to a range of 5.8-6.
2.
54. A method of producing the chitosan material of claim 1, comprising: (a) freeze-drying a first aqueous solution containing chitosan; (b) freeze-drying the second aqueous solution comprising chitosan; (c) obtaining a low density chitosan material having an interconnected porous structure from each of steps (a) and (b); and (d) compressing the low density chitosan material from each of steps (a) and (b); and (e) preparing two layers of chitosan material from the compressed low density chitosan material from each of steps (a) and (b).
55. The method of claim 54, wherein the low density chitosan material from each of steps (a) and (b) is combined prior to compression.
56. The method of claim 54, wherein the compressing of step (d) is carried out at a temperature in the range of 20°C to 150°C.
57. The method of claim 54, further comprising drying the chitosan material to a moisture content of less than 15% (w / w).
58. A method for producing the catechol-modified chitosan material of claim 1, comprising: (a) Controlling the degree of substitution; (b) controlling oxidation levels; and (c) preparing a dry solid catechol-modified chitosan material, wherein the chitosan material resists dissolution in water, saline solution, blood, gastrointestinal fluids or urine at 37°C for at least 6 hours.
Citation Information
Patent Citations
Wound dressings, apparatus, and methods for controlling severe, life-threatening bleeding
US7820872B2
Compositions, assemblies, and methods applied during or after a dental procedure to ameliorate fluid loss and / or promote healing, using a hydrophilic polymer sponge structure such as chitosan
US9004918B2
Degradable haemostat composition
CN105431176A
Catechol chitosan self-healing hydrogel material and preparation method thereof
CN107118357A
Catechol group-contained natural polysaccharide composite hydrogel carrier and preparation method thereof
CN107375196A